Restoration of a Mid-Atlantic Coastal Bay Scallop Population (Argopecten irradians) - Richard A. Snyder; Rebecca T. Smith; Darian M. Kelley; Sean Fate; Robert J. Orth; Bowdoin Lusk; Christopher J. Patrick; Stacy A. Krueger-Hadfield; Jan McDowell; Fredrick C. Holbert; John C. Lewis; John P. Richardson; et al. (Estuaries and Coasts, 2026)
We have attempted to re-establish bay scallops to the Virginia, U.S.A. coastal bays and document the dynamics of the restoration effort. Bay scallops ( Argopecten irradians ) once flourished in the eelgrass ( Zostera marina ) of the Virginia coastal bays. Eelgrass wasting disease led to declines, and both eelgrass and scallops were completely lost after a 1933 hurricane. The Virginia Institute of Marine Science (VIMS) led a successful eelgrass restoration effort beginning in 1997, with eelgrass beds expanding at 204 ha per year since 2012 and covering over 4,800 ha in 2025. From 2009 to 2025, bay scallops were brought in from North Carolina, New York, and Florida to the VIMS Eastern Shore Laboratory (VIMS ESL) in Wachapreague, VA and used to raise bay scallops for restoration. Progeny were released to the eelgrass beds and held in spawning cages. Annual census data documented low and fluctuating scallop densities from 2012 to 2018. From 2019 to 2025, we have observed continued exponential growth with a current (2024–2025) specific growth rate of µ = 0.468 year − 1 and a population doubling time of 1.48 years. The carrying capacity of the system for the new Virginia bay scallop population remains unknown with the population still in the exponential growth phase. In 2025 the annual census documented an average density of 0.114 scallops m − 2 and maximum recorded local density within 50 m − 2 sampling stations of 0.52 scallops m − 2 . Aggregation within the population was anticipated as necessary for reproductive success and was observed in population data with increasing density.

The role of local winds and a semi-persistent coastal front on the diurnal heat budget in an upwelling bay - April P. Thibodeau; Ryan K. Walter; Piero L.F. Mazzini; Thomas P. Connolly; Christopher A. Edwards; Ian Robbins (Continental Shelf Research, 2026)

Emergence of heartbeat frailty in advanced age II: individual cardiovascular aging trajectories revealed by lifelong echocardiography in male mice - Ismayil Ahmet; Nolan M. Winicki; Jacob S. Roberts; Christopher H. Morrell; Edward G. Lakatta (GeroScience, 2026)

Twelve distinct laboratory methods used to measure SARS-CoV-2 in wastewaters throughout a three-year Ontario-wide, Canada study: Impact on public health interpretation of disease incidence - Nada Hegazy; K. Ken Peng; Johanna de Haan-Ward; Elizabeth Renouf; Elizabeth Mercier; Shen Wan; X. Joan Hu; Charmaine Dean; Mark Servos; Elizabeth Edwards; Gustavo Ybazeta; Marc Habash; et al. (Journal of Water Process Engineering, 2026)

Correction: Structure–Function Parameters Over Different Surface Footprints in Coastal Zones - Andrey A. Grachev; Harindra J. S. Fernando; Stef L. Bardoel; Robb M. Randall; Christopher M. Hocut; Edward D. Creegan; Laura S. Leo (Boundary-Layer Meteorology, 2026)

From the deep sea to the shore: Source fingerprinting and weathering of spilled oil following the 2023 MT Princess Empress oil spill (Oriental Mindoro, Philippines) - Jay Rumen U. Maglupay; Edward S. Yeo; Gerald L. Cordero; Rachel Zioness O. Diputado; Kim Christopher C. Aganda; Rodolfo A. Romarate; Julien Guyomarch; Chin-Chang Hung; Hernando P. Bacosa (Marine Pollution Bulletin, 2026)

Associations between space-use behaviour and temperature-humidity index in barn-housed dairy cows - Kareemah Chopra; Chenyu Zhang; Chunde Liu; Zhiwen Luo; Christopher K. Reynolds; Jonathan R. Amory; Zoe E. Barker; Andy Thurman; Edward A. Codling (Applied Animal Behaviour Science, 2026)

Structure–Function Parameters Over Different Surface Footprints in Coastal Zones - Andrey A. Grachev; Harindra J. S. Fernando; Stef L. Bardoel; Robb M. Randall; Christopher M. Hocut; Edward D. Creegan; Laura S. Leo (Boundary-Layer Meteorology, 2026)
High frequency turbulent data from sonic anemometers and other ancillary information collected at multiple levels on several meteorological flux towers located at two coastal sites are used to study velocity and scalar (temperature and humidity) structure–function parameters over heterogeneous surfaces in an area of complex coastal terrains. Understanding of such parameters has important applications for studies on wave propagation in a turbulent atmosphere. One observational site was located on the Outer Banks near the town of Duck, North Carolina, with data from the CASPER-East Program (October–November 2015). The second site was located near the town of Ferryland, Newfoundland, Canada, with data from the C-FOG (Coastal-Fog) field campaign (September–October 2018). These measurements allowed studies of structure parameters and other statistics for different footprints, including relatively smooth sea surface conditions and aerodynamically rough dry inland areas for both stable and unstable stratifications. The coastal land cover discontinuity for onshore and offshore winds leads to a thin internal boundary layer (IBL) that could often be resolved by the instrumented towers. The drag coefficient, Bowen ratio, and diurnal variation of sensible heat flux were found to be coastal IBL markers. Our study shows that lower values of the dimensional structure parameters are associated with higher altitudes, smooth surfaces (i.e., over water, outside onshore IBL) and stable stratification (e.g., nocturnal boundary layer), ceteris paribus. In particular, observations showed that the structure parameters over land footprint areas (inside the onshore IBL) can be an order of magnitude larger than over the sea surface due to the change of aerodynamic and thermal properties of the surface. This study also discusses the applicability of Monin–Obukhov similarity theory (MOST) for the velocity and scalar structure parameters in the coastal environment for both stable and unstable conditions. While surface inhomogeneities and the complexity of the coastal landforms nominally violate assumptions underlying MOST, our observations show that the nondimensional structure parameters obey MOST reasonably well for all measurement levels, stability condition, and wind direction. In addition, we suggest a new variance-based hybrid scaling for the structure parameters that overcomes some of the shortcomings of the traditional approach (e.g., self-correlation and ambiguity of the dimensionless temperature structure parameter for near-neutral conditions).

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

A laboratory-based spectrometer intercomparison for the measurement of snow spectra - Benjamin M. Roberts-Pierel; Christopher J. Crawford; Steven W. Brown; Raymond F. Kokaly; Kelly E. Gleason; Anne W. Nolin; Edward H. Bair; Brenton A. Wilder; Anton J. Surunis; S. McKenzie K. Skiles; Joachim Meyer; Allyson E. Fitts; et al. (Cold Regions Science and Technology, 2026)

Particulate nitrate over the Northwest Atlantic: Insights gained by comparing airborne AMS and PILS measurements - Soodabeh Namdari; Taiwo Ajayi; Yonghoon Choi; Ewan C. Crosbie; Joshua P. DiGangi; Glenn S. Diskin; Eva-Lou Edwards; Johnathan W. Hair; Christopher A. Hostetler; Simon Kirschler; John B. Nowak; Michael Shook; et al. (Atmospheric Environment, 2026)

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Factors affecting 87Sr/86Sr preservation in conodont apatite: An example from the Ordovician of Baltoscandia - Christopher T. Conwell; Matthew R. Saltzman; Anders Lindskog; Mats E. Eriksson; Elizabeth M. Griffith; Stephen A. Leslie; Cole T. Edwards; Olle Hints; Achim D. Herrmann (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Zooplankton grazing and nutrient supply control the emergence of large diatoms in coastal upwelling systems: Insights from a regional ecosystem model - Jann Paul Mattern; Stephanie Dutkiewicz; Jordyn E. Moscoso; Christopher A. Edwards (Limnology and Oceanography, 2026)
The California Current System (CCS) is characterized by dynamic coastal upwelling that profoundly influences plankton community structure and diversity and that leads to the emergence of large diatoms nearshore. This study presents a high‐resolution biogeochemical model of the CCS, coupling the Darwin ecosystem model with the Regional Ocean Modeling System (ROMS). The model is configured to capture key plankton patterns in the CCS, including chlorophyll distribution, cross‐shore phytoplankton community composition, and ecosystem size structure. We show that the emergence of large diatoms in nutrient‐rich nearshore waters requires both high nutrient availability and robust grazing pressure, a result that aligns with ecological theory and observational studies. The model also shows size quantization patterns in the plankton biomass spectra, which dynamically adjust to changing environmental conditions. Our results highlight the importance of the interplay between bottom‐up and top‐down controls in shaping the planktonic ecosystem, with a specific emphasis on the factors leading to the emergence of large diatoms in the CCS. These findings provide insights into the mechanisms underlying plankton diversity and community structure in coastal upwelling systems, which we can build upon to improve our understanding of ecosystem responses to environmental changes in the CCS and other highly productive coastal regions.

Integrating Cancer Education Into High School Curricula - Jessica Ma; Asher Shin; Ranvir Iyengar; Isabella Nguyen; Lilac Nguyen; Emily Feng; Khushi Kohli; Stephanie Wang; Erin Jay G Feliciano; Edward Christopher Dee; Davidi Tawfiles (Journal of Cancer Education, 2026)

Seascape diversity and configuration shape habitat selection across multiple coastal ecosystems - Jesse D. Mosman; Hayden P. Borland; Ashley J. Rummell; Christopher J. Henderson; Sam Allan; Alec Bannam; Stacy L. Bierwagen; Michael J. Bradley; Alex B. Carter; Daniela M. Ceccarelli; Robert Coles; Michael J. Emslie; et al. (Biological Conservation, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Correction: Importance of near-bottom oceanographic data in modeling the distribution of eulachon bycatch in the U.S. West Coast shrimp trawl fishery - Leif K. Rasmuson; Scott D. Groth; Christopher A. Edwards; Eric S. Anderson; Matthew T.O. Blume; Kendall R. Smith (Frontiers in Marine Science, 2025)

Interaction of bay outflow and wind-driven upwelling in chlorophyll patterns in the Gulf of the Farallones - Candice N. Cooper; Christopher A. Edwards; John L. Largier; Piero L.F. Mazzini (Deep Sea Research Part II: Topical Studies in Oceanography, 2025)

Rapid parameter inference with uncertainty quantification for a radiological plume source identification problem - Christopher Edwards; Ralph C. Smith (Environmental and Ecological Statistics, 2025)

Congener Conflict: Invasive Barred Owl Landscape Use Across the Range of the Northern Spotted Owl - Julianna M. A. Jenkins; Natalie M. Rugg; Raymond J. Davis; Scott A. Gremel; Aaron Henderson; Edward Henson; Mark Higley; Holly D. Horan; Christopher McCafferty; Thomas Munger; David Press; Suzanne Reffler; et al. (Journal of Biogeography, 2025)
Aim To map the probability of landscape use of invading barred owls ( Strix varia ) across the range of the threatened northern spotted owl ( S. Occidentallis Caurina ) in the Pacific Northwest, USA , identifying environmental drivers of barred owl landscape use to inform targeted management interventions. Location Forests of the Pacific Northwest, USA. Taxon Barred Owl ( Strix varia ). Methods We deployed 4081 autonomous recording units ( ARUs ) within 1027 randomly selected long‐term monitoring sites consisting of 5‐km 2 hexagons in 2023. We processed audio recordings using convolutional neural networks to detect vocalisations. We applied single‐season occupancy models at both ARU station and hexagon scales to estimate barred owl landscape use and assess associations with environmental variables. Using top models, we mapped barred owl landscape use across the full US range of the northern spotted owl, an umbrella species for conservation of the pacific northwest old‐growth forest community. Results Barred owls were widely detected, with naïve occupancy at 86.8% at the 5‐km 2 hexagon scale. We observed regional variation, with the highest landscape use in the Oregon Coast region and lower landscape use in California regions and the Washington Eastern Cascades. Landscape use was positively associated with mature forest characteristics at both broad and fine scales and negatively associated with elevation and climatic water deficit. Cumulative detection probability exceeded 90% after 2 weeks at the hexagon scale and 4 weeks at the station scale, providing guidance for future barred owl monitoring efforts. Main Conclusions Our study reveals extensive, but not ubiquitous, barred owl distribution across the range of the northern spotted owl. The findings offer a decision‐support framework for prioritising targeted management actions, particularly in regions with lower rates of barred owl landscape use. The integration of passive acoustic monitoring and AI‐based detection demonstrates a scalable approach for invasive species monitoring and conservation planning to meet management objectives in dynamic forest landscapes.

Permafrost Thaw Accelerates Old Soil Carbon Release, Outpacing New Plant Inputs During a 13‐Year Tundra Warming Experiment - Emma Lathrop; Craig See; Xanthe Walker; Grant Falvo; Zev Axler; Christopher Ebert; Stephanie Kadej; Allison Kelley; Justin Ledman; Sophie Opfergelt; Heidi Rodenhizer; Edward A. G. Schuur (Global Change Biology, 2025)
Massive stores of ancient soil organic carbon (SOC) in permafrost can decompose with Arctic warming and accelerate global climate change. Declining SOC stocks are central to the permafrost carbon feedback, but direct measures of SOC loss are extremely rare due to methodological challenges related to subsidence in the Arctic. To fully capture changing SOC dynamics during thaw, we directly measured SOC stock and bulk soil radiocarbon ( 14 C) changes, while accounting for subsidence, during 13 years of permafrost thaw in a warming experiment in Interior Alaska. We found significant declines in SOC stocks: 14% (± 6%) in ambient plots that experienced regional warming and 23% (± 5%) in snow fence warmed plots, entirely in deep, mineral soil layers. Losses were largely driven by winter soil warming but were mediated by changing soil moisture and vegetation conditions. Plots with low shrub biomass had greater SOC losses, suggesting that vegetation community composition may play an important role in SOC storage. Surface soil 14 C measurements suggest that carbon inputs were three times greater in warming plots compared to ambient plots, but that decomposition increased proportionally leading to no detectable change in surface organic layers. We observed significant SOC losses of 5.2–8.1 kg C m −2 from deeper soil layers where carbon was sequestered ~2400 to ~4500 years ago. Our findings indicate that warmer soils in the winter will accelerate SOC losses, but that increasing density of shrub species through shrub expansion could help to mitigate SOC losses in deep soils. The significant loss of SOC from deep, mineral soils observed over just 13 years of ambient and experimental permafrost thaw highlights the vulnerability of this old C pool as it enters the active global carbon cycle.

Angiotensin II, miR-34a, and AGTRAP crosstalk in arterial smooth muscle cells - Maria Cristina Florio; Sara Sileno; Liqun Jiang; Marco D’Agostino; Sunayana Begum Syed; Laura Monteonofrio; Mirko Baranzini; Chiara Prampolini; Federica Macrì; Manuel Casaburo; Nadia Fanotti; Stefania Castiglione; et al. (GeroScience, 2025)
Arterial aging is associated with enhanced angiotensin II (Ang II) signaling via Ang II type 1 receptor (AT1R) and with microRNA-34a (miR-34a) increased expression. AT1R-associated protein (ATRAP/Agtrap) binds to AT1R, promotes its internalization, and inhibits Ang II signaling. This study addresses the hypothesis that miR-34a targets ATRAP/Agtrap and enhances Ang II pro-inflammatory signaling via AT1R in arterial vascular smooth muscle cells (VSMC). Our results show that miR-34a exhibits an age-associated increase in Rhesus monkey’s common carotid artery and rat aorta. Further, AGTRAP protein expression is lower in old rat VSMC and in old mice aorta. Ang II enhances miR-34a in old rat VSMC and human aortic smooth muscle cells (HASMC), and inhibits AGTRAP and sirtuin 1 (SIRT1) mRNA/protein expression. In miR-34a-overexpressing HASMC, AGTRAP and SIRT1 mRNA/protein decrease, and these effects are rescued by AGTRAP forced expression. Moreover, miR-34a directly targets AGTRAP and AGTRAP downmodulation further enhances miR-34a expression decreasing SIRT1 in HASMC. Finally, Ang II and miR-34a induce the upregulation of pro-inflammatory genes, interleukin (IL)-6, cyclooxygenase 2 (COX2), monocyte chemoattractant protein-1 (MCP-1), and milk fat globule-epidermal growth factor 8 (MFGE8) in HASMC, and this effect is abolished by AGTRAP forced expression. In conclusion, Ang II upregulates miR-34a, activating a negative feedback loop on AGTRAP that reinforces Ang II signaling. The age-associated AGTRAP downmodulation in central arteries and VSMC underlies a potential miR-34a/AGTRAP role in vascular aging.

Importance of near-bottom oceanographic data in modeling the distribution of eulachon bycatch in the U.S. West Coast shrimp trawl fishery - Leif K. Rasmuson; Scott D. Groth; Christopher A. Edwards; Eric S. Anderson; Matthew T.O. Blume; Kendall R. Smith (Frontiers in Marine Science, 2025)
Introduction Species distribution models (SDMs) are increasingly used in fisheries science to understand species’ spatial patterns and improve stock assessments. Method This study developed SDMs for eulachon smelt ( Thaleichthys pacificus ), a threatened, demersal forage fish often caught as bycatch in the United States West Coast ocean shrimp trawl fishery. Using ten years of observer data (2012–2021, n=19,749 with 25.4% being zeros), the study assessed the influence of static (e.g., substrate) and dynamic (e.g., ocean temperature, currents) environmental variables on eulachon abundance. Results The best-performing SDM included near-bottom temperature and current data, outperforming SDMs using only surface variables. Eulachon abundance peaked at ~150 m depth, especially over gravel substrates, and during nighttime. Although none of the SDM-based abundance indices significantly correlated with the Columbia River stock assessment index, bottom-based SDMs showed stronger alignment with the stock assessment (R=0.61, p=0.08 & R=0.62, p=0.07). Discussion Management implications are significant. Rock habitats were associated with higher eulachon bycatch, and vessels can use bottom-typing tools to avoid them. Also, delaying the season opener could reduce bycatch, as eulachon catch was reduced by 0.0109 mt per trawl over the interquartile range of day of the year. These findings can inform Best Management Practices (BMPs), which have historically led to regulatory changes such as the adoption of excluder grates and LED lights. Overall, incorporating near-bottom oceanographic data greatly enhanced predictive performance, especially for demersal species like eulachon. These mechanistic SDMs can be projected forward, aiding future management amid changing ocean conditions. While some discrepancies remain, this approach offers promising insights for adaptive fishery management and conservation of imperiled species like eulachon.

Seasonal coastal groundwater dynamics in Lahaina beaches, Hawaiʻi: Implications for contaminant transport in a post-wildfire setting - Edward Lopez; Xiaolong Geng; Amir Haroon; Hong Zhang; Yangyang Zou; Tao Yan; Henrietta Dulai; Christopher Shuler (Marine Pollution Bulletin, 2025)

Sliding mode observer based non-causal model predictive control for collision-free marine launch and recovery system - Vincentius Versandy Wijaya; Yao Zhang; Christopher Edwards; Guang Li; Michael Belmont (Ocean Engineering, 2025)

Comparing Navcam dust devil detections to transient daytime convective vortex signatures in REMS pressure and ultraviolet data - Emily L. Mason; Scott D. Guzewich; Christopher Edwards; Álvaro Vicente-Retortillo; Daniel Viúdez-Moreiras (Icarus, 2025)

Integration of crop modeling and sensing into molecular breeding for nutritional quality and stress tolerance - Jonathan Berlingeri; Abelina Fuentes; Earl Ranario; Heesup Yun; Ellen Y. Rim; Oscar Garrett; Alexander Howard; Mary-Francis LaPorte; Sassoum Lo; Duke Pauli; Jenna Hershberger; Mason Earles; et al. (Theoretical and Applied Genetics, 2025)
Integrating innovative technologies into plant breeding is critical to bolster food and nutritional security under biotic and abiotic stresses in changing climates. While breeding efforts have focused primarily on yield and stress tolerance, emerging evidence highlights the need to also prioritize nutritional quality. Advanced molecular breeding approaches have enhanced our ability to develop improved crop varieties and could be substantially informed by the routine integration of crop modeling and remote sensing technologies. This review article discusses the potential of combining crop modeling and sensing with molecular breeding to address the dual challenge of nutritional quality and stress tolerance. We provide overviews of stress response strategies, challenges in breeding for quality traits, and the use of environmental data in genomic prediction. We also describe the status of crop modeling and sensing technologies in grain legumes, rice, and leafy greens, alongside the status of -omics tools in these crops and the use of AI with directed evolution to identify novel resistance genes. We describe the pairwise and three-way integration of AI-enabled sensing and biophysically and empirically constrained crop modeling into breeding to enable prediction of phenotypic and breeding values and dissection of genotype-by-environment-by-management interactions with increasing fidelity, efficiency, and temporal/spatial resolution to inform selection decisions. This article highlights current initiatives and future trends that focus on leveraging these advancements to develop more climate-resilient and nutritionally dense crops, ultimately enhancing the effectiveness of molecular breeding.

Failure of efficient cardiac proteostatic adaptations to chronic cAMP-stress is associated with accelerated heart aging - Maria Grazia Perino; Miguel Calvo-Rubio Barrera; Daniel R. Riordon; Giulio Agnetti; Alexander Maltsev; Admira Parveen; Christopher H. Morrell; Ismayil Ahmet; Khalid Chakir; Yelena S. Tarasova; Jia-Hua Qu; Kirill V. Tarasov; et al. (GeroScience, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Heat stress monitoring, modelling, and mitigation in a dairy cattle building in reading, UK: Impacts of current and projected heatwaves - Chunde Liu; Yiran Cao; Zhiwen Luo; Yiqing Liu; Christopher K. Reynolds; David Humphries; Chenyu Zhang; Edward A. Codling; Kareemah Chopra; Jonathan Amory; Zoe Barker (Building and Environment, 2025)

Clearance of particles from regular-flavored little cigar smoke across lung lobes in female Sprague-Dawley rats - Kaisen Lin; Christopher Wallis; Patricia Edwards; Austin Cole; Laura Van Winkle; Anthony S. Wexler (Journal of Aerosol Science, 2025)

Informatics for toxicokinetics - Gilberto Padilla Mercado; Christopher Cook; Norman Adkins; Lucas Albrecht; Grace Cary; Brenda Edwards; Derik E. Haggard; Nancy M. Hanley; Michael F. Hughes; Anna Jarnagin; Tirumala D. Kodavanti; Evgenia Korol-Bexell; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Tropical Land‐Use Change Disrupts Zeta‐Diversity Across Taxa - Edicson Parra‐Sanchez; Guillaume Latombe; Simon C. Mills; Jacob B. Socolar; Felicity A. Edwards; Diego Martinez‐Revelo; Oscar A. Perez‐Escobar; Robert W. Davies; Christopher G. Bousfield; Gianluca R. Cerullo; Jose Manuel Ochoa‐Quintero; Torbjørn Haugaasen; et al. (Global Change Biology, 2025)
Land‐use change causes community turnover via local extinction and colonisation of species, driving biotic homogenization or heterogenization at larger spatial scales. Quantification of these processes has focused on beta‐diversity metrics, which upweight rarity and overlook the role of widespread species. A key knowledge gap is understanding the impact of land‐use change on both rare and widespread species—zeta‐diversity—allowing the detection of statistical patterns and drivers based on community turnover across space. We sampled bird, dung beetle, and orchid communities in 341 plots across natural (Andean forests and paramo) and transformed habitats (pasturelands) spanning ~270 km north‐to‐south in the Colombian Andes. We detected major losses in species richness following land‐use conversion, which disrupts zeta‐diversity across elevation in two ways. First, biodiversity patterns are rewired such that bird and dung beetle communities become structured by dispersal ability, overriding the effects of natural biogeographical drivers (i.e., elevation) and landscape conditions (i.e., canopy cover). Second, land‐use change causes biotic homogenization across bird communities, with pasture retaining twice as many widespread species than natural habitats, and a four‐fold reduction in widespread dung beetle species pointing to subtractive heterogenization. Orchid communities show high community turnover in both natural and transformed habitat. Our results show that the effect of local deforestation has a doubly devastating impact simplifying communities and reducing widespread species. Transforming natural habitats into anthropogenic landscapes may substantially raise extinction risk for communities composed of both widespread and rare species, especially in orchids as the most sensitive taxon.

A Review of Global Fisheries Performance - Frank Asche; Taryn M. Garlock; James L. Anderson; Ruth B. Pincinato; Christopher M. Anderson; Edward V. Camp; Jingjie Chu; Andreea L. Cojocaru; Hakan Eggert; Kai Lorenzen; David C. Love; Ragnar Tveteras (Fish and Fisheries, 2025)
Management of fisheries is complex as it combines environmental, economic and social objectives. The relative importance of these objectives is highly debated and the best approaches to achieving good outcomes are unclear. A lack of global and multi‐dimensional data has largely precluded reviews providing comparisons of performances across systems at a large scale. We review fisheries performance by analysing outcomes over 14 dimensions of environmental, economic and community performance using a unique global dataset for 145 fisheries collected with the Fishery Performance Indicators. The fisheries are ranked into three performance groups by an average of their environmental, economic and community scores: the 10% best fisheries, the 10% worst fisheries and the middle 80%. Furthermore, we investigate how four different types of management systems, catch shares, territorial use rights, limited entry and open access, are represented in the three performance groups. The best performing fisheries scored equally or better and the poorest performing fisheries scored equally or worse in environmental, economic and social dimensions. We found three different management systems to be represented among the best performing fisheries, indicating that no specific management system is best. Moreover, some management systems were represented in all three performance categories, indicating that fisheries characteristics or management designs are important elements of fishery performance. The worst performing fisheries were dominated by open access fisheries with no or very limited management.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Reproductive characteristics of the big blue octopus, Octopus cyanea (Gray 1849) in Zanzibar coastal waters, Tanzania - Amini Ismail Hamad; Batuli Yahya; Edward Moto; Christopher Muhando (Western Indian Ocean Journal of Marine Science, 2025)
The big blue octopus, Octopus cyanea (Gray 1849) is heavily fished in Zanzibar coastal waters, yet several aspects of its biology remain unstudied in the area. The reproductive biology of O. cyanea (Gray 1849) was investigated, including sex ratios, length-weight relationships, size at maturity, and seasonal variation in maturity and spawning activity. Sampling of specimens caught by local fishers was conducted monthly at four sites. Octopus size and weight were measured and the sex determined, whereafter their gonads were extracted and staged. Female octopuses dominated the sex ratio across most size classes and seasons. Males reached sexual maturity at a smaller size than females and mature individuals of both sexes were present throughout the year, suggesting continuous spawning activity. Based on the gonadosomatic index (GSI), peak spawning periods were in June and October. The new insights into the reproductive dynamics of O. cyanea are important for fisheries management efforts and effective conservation of the species.

Correction: Sequence Divergence in Venom Genes Within and Between Montane Pitviper (Viperidae: Crotalinae: Cerrophidion) Species is Driven by Mutation–Drift Equilibrium - Ramses Alejandro Rosales‑Garcia; Rhett M. Rautsaw; Erich P. Hofmann; Christoph I. Grünwald; Hector Franz‑Chavez; Ivan T. Ahumada‑Carrillo; Ricardo Ramirez‑Chaparro; Miguel Angel de la Torre‑Loranca; Jason L. Strickland; Andrew J. Mason; Matthew L. Holding; Miguel Borja; et al. (Journal of Molecular Evolution, 2025)

Opportunity to Leverage Tactics Used by Skilled Fishers to Address Persistent Bycatch Challenges - Leslie A. Roberson; Christopher J. Brown; Carissa J. Klein; Edward T. Game; Chris Wilcox (Fish and Fisheries, 2025)
Effective management of shark bycatch is urgently needed to reverse widespread population declines, especially in longline fisheries that are estimated to be responsible for half of global shark catch. Management of shark catch typically focuses on the safe release of landed sharks, with limited attention to reducing the initial catch. Where controls on fishing effort or catch do exist, management frameworks tend to treat fishing fleets as homogeneous units. The underlying assumption is that fishers have similar abilities to catch target species and avoid bycatch. We test this assumption by analysing variability in shark bycatch rates among individual vessels in an industrial tuna longline fleet operating in the Western Pacific. Controlling for factors such as geographic location, time of day and gear depth, we find that individual vessels drive highly variable bycatch rates of blue ( Prionace glauca ) and silky sharks ( Carcharhinus falciformis ) – two shark species with the highest global catch volumes. Additionally, we found that the operating company can influence fisher performance. As countries and regional organisations increasingly adopt shark conservation plans and make international conservation commitments, it is crucial to identify viable new strategies that do not unduly burden the industry or penalise good actors. Tailoring management actions to individual fishers and companies – holding high‐bycatch fishers accountable and incentivising low‐bycatch fishers to continuously improve – presents a crucial opportunity to address the overfishing of sharks and other global bycatch challenges.

Routine large-scale movements of the yelloweye rockfish (Sebastes ruberrimus) - Leif K. Rasmuson; Matthew T. O. Blume; Kelly A. Lawrence; Bruce M. Laughlin; Christopher A. Edwards; Mark R. Terwilliger; A. Camille Ayrea; Alexandra G. McInturf; Bryan J. Legare; Taylor K. Chapple (Frontiers in Marine Science, 2025)
Of the seven species of Pacific rockfish declared overfished in the California Current in 2008, yelloweye rockfish ( Sebastes ruberrimus ) is the only remaining overfished rockfish species. Part of the original rebuilding plan included designation of a yelloweye rockfish conservation area, a rocky reef closed off the Central Coast of Oregon that is closed to bottom fishing. The yelloweye rockfish conservation area’s ability to help rebuild the population, is predicated on the theory that demersal rockfishes are relatively sedentary. However, in the years since being declared overfished, acoustic tagging studies suggested yelloweye rockfish did not remain in the yelloweye rockfish conservation area. However, where they went remained a mystery. In this paper we describe the use of pop-off satellite tags to conduct a mark-recapture study of 11 yelloweye rockfish tagged within the Stonewall Bank Yelloweye Rockfish Conservation Area. We used back-in-time particle tracking coupled with an ocean circulation model in an attempt to increase the precision in the location at which each tag shed off the fish, and further validated that location by associating it to the underlying seafloor habitat type. Ten out of eleven tags were shed from the fish while it was outside the Stonewall Bank Yelloweye Rockfish Conservation Area’s boundary. While most fish remained within 50 km of the Stonewall Bank Yelloweye Rockfish Conservation Area, one tagged fish swam to an offshore reef off Central Washington (~40 km from the shore). Backtracked locations were more likely over rock than the initial satellite transmission, indicating the method was effective at identifying tag shed locations. We found no relationship between days at large, fish sex or length and the distance between release site and shed location. Our work supports a growing body of work that suggests yelloweye rockfish have less site fidelity than previously hypothesized.

Reproducibility of Semi-automated Quantitative Analyses of Tc-99m Pyrophosphate Uptake from Myocardial Perfusion Planar and SPECT Images - Divyani Goyal; Veronica Sandoval; Christopher Weyman; Edward J. Miller; Yi-Hwa Liu (Journal of Medical and Biological Engineering, 2025)

Dietary Fiber Intake and Risk of Advanced and Aggressive Forms of Prostate Cancer: A Pooled Analysis of 15 Prospective Cohort Studies - Elkhansa Sidahmed; Stephen J. Freedland; Molin Wang; Kana Wu; Demetrius Albanes; Matt Barnett; Piet A. van den Brandt; Michael B. Cook; Graham G. Giles; Edward Giovannucci; Christopher A. Haiman; Susanna C. Larsson; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

On the impact of the vertical structure of Martian water ice clouds on nadir atmospheric retrievals from simultaneous EMM/EXI and TGO/ACS-MIR observations. - Aurélien Stcherbinine; Michael J. Wolff; Christopher S. Edwards; Oleg Korablev; Anna Fedorova; Alexander Trokhimovskiy (Icarus, 2025)

Numeric ring-reconstructions based on massifs favor a non-oblique south pole-Aitken-forming impact event - Hannes Bernhardt; Jessica M. Walsh; Leon M. Schröder; Jaclyn D. Clark; Megan R. Henriksen; Christopher S. Edwards (Earth and Planetary Science Letters, 2025)

Emergency Department Patients Presenting after Oral versus Inhaled Cannabinoid use: A Retrospective Analysis - Tony Zitek; Christopher Raciti; Alvin Nguyen; Valentina Roa; Edward Lopez; Gregory Oliva; David A. Farcy (Journal of Medical Toxicology, 2025)

Controls on spatial variation in porewater methane concentrations across United States tidal wetlands - Erika L. Koontz; Sarah M. Parker; Alice E. Stearns; Brian J. Roberts; Caitlin M. Young; Lisamarie Windham-Myers; Patricia Y. Oikawa; J. Patrick Megonigal; Genevieve L. Noyce; Edward J. Buskey; R. Kyle Derby; Robert P. Dunn; et al. (Science of The Total Environment, 2024)

Global survey of paleo-bedforms on Mars - Matthew Chojnacki; Lori K. Fenton; Lauren A. Edgar; Mackenzie Day; Christopher S. Edwards; Aaron R. Weintraub; Amber L. Gullikson; Matt W. Telfer (Geomorphology, 2024)

Assessing impacts of observations on ocean circulation models with examples from coastal, shelf, and marginal seas - Christopher A. Edwards; Pierre De Mey-Frémaux; Bàrbara Barceló-Llull; Guillaume Charria; Byoung-Ju Choi; George R. Halliwell; Lars R. Hole; Colette Kerry; Vassiliki H. Kourafalou; Alexander L. Kurapov; Andrew M. Moore; Baptiste Mourre; et al. (Frontiers in Marine Science, 2024)
Ocean observing systems in coastal, shelf and marginal seas collect diverse oceanographic information supporting a wide range of socioeconomic needs, but observations are necessarily sparse in space and/or time due to practical limitations. Ocean analysis and forecast systems capitalize on such observations, producing data-constrained, four-dimensional oceanographic fields. Here we review efforts to quantify the impact of ocean observations, observing platforms, and networks of platforms on model products of the physical ocean state in coastal regions. Quantitative assessment must consider a variety of issues including observation operators that sample models, error of representativeness, and correlated uncertainty in observations. Observing System Experiments, Observing System Simulation Experiments, representer functions and array modes, observation impacts, and algorithms based on artificial intelligence all offer methods to evaluate data-based model performance improvements according to metrics that characterize oceanographic features of local interest. Applications from globally distributed coastal ocean modeling systems document broad adoption of quantitative methods, generally meaningful reductions in model-data discrepancies from observation assimilation, and support for assimilation of complementary data sets, including subsurface in situ observation platforms, across diverse coastal environments.

A sustainable blue economy may not be possible in Tanzania without cutting emissions - Ana M. Queirós; Elizabeth Talbot; Flower E. Msuya; Baraka Kuguru; Narriman Jiddawi; Shigalla Mahongo; Yohana Shaghude; Christopher Muhando; Elias Chundu; Zoe Jacobs; Sevrine Sailley; Elina A. Virtanen; et al. (Science of The Total Environment, 2024)

Optimizing photosynthetic light-harvesting under stars: simple and general antenna models - Samir Chitnavis; Callum Gray; Ifigeneia Rousouli; Edward Gillen; Conrad W. Mullineaux; Thomas J. Haworth; Christopher D. P. Duffy (Photosynthesis Research, 2024)
In the next 10–20 years, several observatories will aim to detect the signatures of oxygenic photosynthesis on exoplanets, though targets must be carefully selected. Most known potentially habitable exo-planets orbit cool M-dwarf stars, which have limited emission in the photosynthetically active region of the spectrum (PAR, $$400< λ < 700$$ 400 < λ < 700 nm) used by Earth’s oxygenic photoautotrophs. Still, recent experiments have shown that model cyanobacteria, algae, and non-vascular plants grow comfortably under simulated M-dwarf light, though vascular plants struggle. Here, we hypothesize that this is partly due to the different ways they harvest light, reflecting some general rule that determines how photosynthetic antenna structures may evolve under different stars. We construct a simple thermodynamic model of an oxygenic antenna-reaction centre supercomplex and determine the optimum structure, size and absorption spectrum under light from several star types. For the hotter G (e.g. the Sun) and K-stars, a small modular antenna is optimal and qualitatively resembles the PSII-LHCII supercomplex of higher plants. For the cooler M-dwarfs, a very large antenna with a steep ’energy funnel’ is required, resembling the cyanobacterial phycobilisome. For the coolest M-dwarfs an upper limit is reached, where increasing antenna size further is subject to steep diminishing returns in photosynthetic output. We conclude that G- and K-stars could support a range of niches for oxygenic photo-autotrophs, including high-light adapted canopy vegetation that may generate detectable bio-signatures. M-dwarfs may only be able to support low light-adapted organisms that have to invest considerable resources in maintaining a large antenna. This may negatively impact global coverage and therefore detectability.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

In-situ observations of resident space objects with the CHEOPS space telescope - Nicolas Billot; Stephan Hellmich; Willy Benz; Andrea Fortier; David Ehrenreich; Christopher Broeg; Alexis Heitzmann; Anja Bekkelien; Alexis Brandeker; Yann Alibert; Roi Alonso; Tamas Bárczy; et al. (Journal of Space Safety Engineering, 2024)

Hot and Fresh: Evidence of Climate-Related Suboptimal Water Conditions for Seagrass in a Large Gulf Coast Estuary - Marcus W. Beck; Kerry Flaherty-Walia; Sheila Scolaro; Maya C. Burke; Bradley T. Furman; David J. Karlen; Christopher Pratt; Christopher J. Anastasiou; Edward T. Sherwood (Estuaries and Coasts, 2024)
Seagrasses have long been a focal point for management efforts aimed at restoring ecosystem health in estuaries worldwide. In Tampa Bay, Florida (USA), seagrass coverage has declined since 2016 by nearly a third (11,518 acres), despite sustained reductions of nitrogen loads supportive of light environments for growth. Changing physical water quality conditions related to climate change may be stressing seagrasses beyond their optimal growth ranges, requiring an assessment to determine if this decline can be linked to climate stress. Three ambient water quality datasets of varying sampling designs and coverage were evaluated to characterize physicochemical environments in Tampa Bay and the potential relationships with seagrass change. Tampa Bay has become hotter and fresher with water temperature increasing by 0.03–0.04 °C per year and salinity decreasing by 0.04–0.06 ppt per year, translating to an increase of 1.3 to 1.7 °C and a decrease of 1.6 to 2.6 ppt over the last 50 years. Additionally, the number of days when temperature was above 30 °C or salinity was below 25 ppt has increased on average across all bay segments by 48 and 37 days, respectively, since 1975. These changes varied spatially and seasonally, with the most dramatic changes observed in the upper bay. Generalized Additive Models provided a weight-of-evidence that recent seagrass declines are somewhat associated with hotter and fresher conditions. Trends in warming and increased precipitation in the region are likely to continue, further creating suboptimal conditions for seagrasses in Tampa Bay. These results should compel resource managers to consider the likelihood that reduced resilience of estuarine resources due to shifting ecological baselines driven by additional climate change drivers will complicate long-standing management paradigms. While conventional management approaches that focus on limiting nutrient loads should be continued, their future effectiveness may be confounded by climate change drivers and warrant additional, complementary interventions and continuous monitoring data to support ecosystem health into the future.

A 561-yr (1461-2022 CE) summer temperature reconstruction for Mid-Atlantic-Northeast USA shows connections to volcanic forcing and atmospheric circulation - Grant L. Harley; Justin T. Maxwell; Karen E. King; Shelly A. Rayback; Edward R. Cook; Christopher Hansen; R. Stockton Maxwell; Frederick Reinig; Jan Esper; Tsun Fung Au; Ellen V. Bergan; Katherine E. Brings; et al. (Climatic Change, 2024)
Contextualizing current increases in Northern Hemisphere temperatures is precluded by the short instrumental record of the past ca. 120 years and the dearth of temperature-sensitive proxy records, particularly at lower latitudes south of <50 °N. We develop a network of 29 blue intensity chronologies derived from tree rings of Tsuga canadensis (L.) Carrière and Picea rubens Sarg. trees distributed across the Mid-Atlantic and Northeast USA (MANE)—a region underrepresented by multi-centennial temperature records. We use this network to reconstruct mean March-September air temperatures back to 1461 CE based on a model that explains 62% of the instrumental temperature variance from 1901−1976 CE. Since 1998 CE, MANE summer temperatures are consistently the warmest within the context of the past 561 years exceeding the 1951−1980 mean of +1.3 °C. Cool summers across MANE were frequently volcanically forced, with significant ( p <0.05) temperature departures associated with 80% of the largest tropical ( n =13) and extratropical ( n =15) eruptions since 1461 CE. Yet, we find that more of the identified cool events in the record were likely unforced by volcanism and either related to stochastic variability or atmospheric circulation via significant associations ( p <0.05) to regional, coastal sea-surface temperatures, 500-hpa geopotential height, and 300-hpa meridional and zonal wind vectors. Expanding the MANE network to the west and south and combining it with existing temperature-sensitive proxies across North America is an important next step toward producing a gridded temperature reconstruction field for North America.

Spatial and temporal variability of martian water-ice cloud effective radius in EMIRS thermal infrared observations - Samuel A. Atwood; Michael D. Smith; Michael J. Wolff; Khalid Badri; Christopher S. Edwards; Philip R. Christensen; Alain S.J. Khayat; M.R. El-Maarry (Icarus, 2024)

Impacts of exercise on inflammatory markers in individuals with OSA: more questions than answers - Christopher E. Kline; Bradley A. Edwards (Sleep and Biological Rhythms, 2024)

Transient, context‐dependent fitness costs accompanying viral resistance in isolates of the marine microalga Micromonas sp. (class Mamiellophyceae) - Anamica Bedi de Silva; Shawn W. Polson; Christopher R. Schvarcz; Grieg F. Steward; Kyle F. Edwards (Environmental Microbiology, 2024)
Marine microbes are important in biogeochemical cycling, but the nature and magnitude of their contributions are influenced by their associated viruses. In the presence of a lytic virus, cells that have evolved resistance to infection have an obvious fitness advantage over relatives that remain susceptible. However, susceptible cells remain extant in the wild, implying that the evolution of a fitness advantage in one dimension (virus resistance) must be accompanied by a fitness cost in another dimension. Identifying costs of resistance is challenging because fitness is context‐dependent. We examined the context dependence of fitness costs in isolates of the picophytoplankton genus Micromonas and their co‐occurring dsDNA viruses using experimental evolution. After generating 88 resistant lineages from two ancestral Micromonas strains, each challenged with one of four distinct viral strains, we found resistance led to a 46% decrease in mean growth rate under high irradiance and a 19% decrease under low. After a year in culture, the experimentally selected lines remained resistant, but fitness costs had attenuated. Our results suggest that the cost of resistance in Micromonas is dependent on environmental conditions and the duration of population adaptation, illustrating the dynamic nature of fitness costs of viral resistance among marine protists.

Deliberately introduced dung beetles in A ustralia: 12 years of occurrence and abundance records from 2001 to 2022 - Jacob D. Berson; Penelope B. Edwards; T. James Ridsdill‐Smith; Christopher K. Taylor; Daniel J. Anderson; Nigel R. Andrew; Russell A. Barrow; David A. Cousins; Robert N. Emery; Laura L. Fagan; Rhiannon M. Foster; Lucas G. Harwood; et al. (Ecology, 2024)
Since 1968, the Australian Dung Beetle Project has carried out field releases of 43 deliberately introduced dung beetle species for the biological control of livestock dung and dung‐breeding pests. Of these, 23 species are known to have become established. For most of these species, sufficient time has elapsed for population expansion to fill the extent of their potential geographic range through both natural and human‐assisted dispersal. Consequently, over the last 20 years, extensive efforts have been made to quantify the current distribution of these introduced dung beetles, as well as the seasonal and spatial variation in their activity levels. Much of these data and their associated metadata have remained unpublished, and they have not previously been synthesized into a cohesive dataset. Here, we collate and report data from the three largest dung beetle monitoring projects from 2001 to 2022. Together, these projects encompass data collected from across Australia, and include records for all 23 species of established dung beetles introduced for biocontrol purposes. In total, these data include 22,718 presence records and 213,538 absence records collected during 10,272 sampling events at 546 locations. Most presence records (97%) include abundance data. In total, 1,752,807 dung beetles were identified as part of these data. The distributional occurrence and abundance data can be used to explore questions such as factors influencing dung beetle species distributions, dung beetle biocontrol, and insect‐mediated ecosystem services. These data are provided under a CC‐BY‐NC 4.0 license and users are encouraged to cite this data paper when using the data.

Exploration of individual colorectal cancer cell responses to H2O2 eustress using hopping probe scanning ion conductance microscopy - Dong Wang; Emily Woodcock; Xi Yang; Hiromi Nishikawa; Elena V. Sviderskaya; Masanobu Oshima; Christopher Edwards; Yanjun Zhang; Yuri Korchev (Science Bulletin, 2024)

Echocardiographic characterization of age- and sex-associated differences in cardiac function and morphometry in nonhuman primates - Maria Cristina Florio; Laura Fusini; Gloria Tamborini; Christopher Morrell; Alise McDonald; Michelle Walcott; Kenneth Ridley; Kelli L. Vaughan; Julie A. Mattison; Mauro Pepi; Edward G. Lakatta; Maurizio C. Capogrossi (GeroScience, 2024)

Correction to: The Kelp Forest Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh‑Dalmau; Nina Larissa Arroyo; Anne M. Bauer‑Civiello; Rodrigo Beas‑Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)

The Kelp Forest ﻿Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh-Dalmau; Nina Larissa Arroyo; Anne M. Bauer-Civiello; Rodrigo Beas-Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)
Marine kelp forests cover 1/3 of our world's coastlines, are heralded as a nature-based solution to address socio-environmental issues, connect hundreds of millions of people with the ocean, and support a rich web of biodiversity throughout our oceans. But they are increasingly threatened with some areas reporting over 90% declines in kelp forest cover in living memory. Despite their importance and the threats they face, kelp forests are entirely absent from the international conservation dialogue. No international laws, policies, or targets focus on kelp forests and very few countries consider them in their national policy. The Kelp Forest Challenge addresses that gap. Together with 252 kelp experts, professionals, and citizens from 25 countries, the Kelp Forest Challenge was developed as a grassroots vision of what the world can achieve for kelp forest conservation. It is a global call to restore 1 million and protect 3 million hectares of kelp forests by 2040. This is a monumental challenge, that will require coordination across multiple levels of society and the mobilization of immense resources. Pledges may therefore include area for protection or restoration, enabling pledges which assist in conservation (funding, equipment, professional expertise, capacity building), or awareness-based pledges which increase awareness or education about kelp forests. Correspondingly, participants may be from government, scientific institutions, private sector, NGOs, community groups, or individuals. This challenge is the beginning of a 17-year mission to save our kelp forests and anyone and any organisation is invited to participate.

The role of living labs in cultivating inclusive and responsible innovation in precision agriculture - Maaz Gardezi; Halimeh Abuayyash; Paul R. Adler; Juan P. Alvez; Rubaina Anjum; Appala Raju Badireddy; Skye Brugler; Pablo Carcamo; David Clay; Ali Dadkhah; Mary Emery; Joshua W. Faulkner; et al. (Agricultural Systems, 2024)

Experimental study on engine and emissions performance of renewable diesel methanol dual fuel (RMDF) combustion - Khanh Duc Cung; Julian Wallace; Vickey Kalaskar; Edward Mike Smith III; Thomas Briggs; Daniel Christopher Bitsis Jr. (Fuel, 2024)

Radon decay product particle radioactivity and oxidative stress biomarkers in patients with COPD - Christopher Romero-Gutierrez; Petros Koutrakis; Man Liu; Carolina L. Zilli Vieira; Brent A. Coull; Edward F. Maher; Junfeng (Jim) Zhang; Eric Garshick (Environmental Research, 2024)

Temperature Thresholds for Leaf Damage from Two Extreme Freeze Events (2018 and 2021) Near the Northern Range Limit of Black Mangroves (Avicennia germinans) in Southeastern North America - Simen Kaalstad; Michael J. Osland; Donna J. Devlin; C. Edward Proffitt; Laura C. Feher; Anna R. Armitage; Richard H. Day; Kathleen M. Swanson; Gordon H. Anderson; Brigid Berger; Just Cebrian; Karen L. Cummins; et al. (Estuaries and Coasts, 2024)

Deforestation for agriculture increases microbial carbon use efficiency in subarctic soils - Julia Schroeder; Tino Peplau; Frank Pennekamp; Edward Gregorich; Christoph C. Tebbe; Christopher Poeplau (Biology and Fertility of Soils, 2024)
Agriculture is likely to expand poleward with climate change, encouraging deforestation for agriculture in subarctic regions, which alters soil physical, chemical and biological properties and potentially affects microbial metabolic efficiency. Deciphering how and by which mechanisms land-use change affects microbial carbon use efficiency (CUE) will enable the development of mitigation strategies to alleviate C losses. We assessed CUE using 18 O-labelled water in a paired-plot approach on soils collected from 19 farms across the subarctic region of Yukon, Canada, comprising 14 pairs of forest-to-grassland conversion and 15 pairs of forest-to-cropland conversion. Microbial CUE significantly increased following conversion to grassland and cropland. Land-use conversion resulted in a lower estimated abundance of fungi, while the archaeal abundance increased. Interestingly, structural equation modelling revealed that increases in CUE were mediated by a rise in soil pH and a decrease in soil C:N ratio rather than by shifts in microbial community composition, i.e. the ratio of fungi, bacteria and archaea. Our findings indicate a direct control of abiotic factors on microbial CUE via improved nutrient availability and facilitated conditions for microbial growth. Overall, this implies that to a certain extent CUE can be managed to achieve a more efficient build-up of stabilised soil organic C (SOC), as reflected in increased mineral-associated organic C under agricultural land use. These insights may also help constrain SOC models that generally struggle to predict the effects of deforestation, something that is likely to take place more frequently in the subarctic.

Observing Ocean Boundary Currents: Lessons Learned from Six Regions with Mature Observational and Modeling Systems - Nadia Ayoub; María Chidichimo; Edward Dever; Xinyu Guo; Marjolaine Krug; Belén Míguez; Tamaryn Morris; Janet Sprintall; Kiyoshi Tanaka; Robert Todd; John Wilkin; Enrique Álvarez-Fanjul; et al. (Oceanography, 2024)
Ocean boundary currents are complex and highly variable systems that play key roles in connecting the open and coastal ocean through cross-slope circulation and upwelling of nutrient-rich water. The structure, strength, and variability of boundary currents are associated with a broad range of spatial and temporal scales. For that reason, long-term boundary current monitoring is challenging and requires the use of complementary observing platforms and sensors coupled with numerical simulations. The Ocean Observations Physics and Climate Panel Boundary Systems Task Team recently held a virtual dialogue series to discuss six mature boundary current monitoring systems. The goal of the series was to examine strategies for developing a conceptual design for sustained observing activities applicable to a wide range of boundary current systems. This article provides a brief overview of the six systems, including users and the observational and modeling components needed to achieve scientific, operational, and societal goals. Ocean observing best practices and recommendations are shared to provide guidance for the coordination and sustainability of observing systems at ocean boundaries and to strengthen and integrate partnerships across and within the global observing networks.

Diverse pathways for climate resilience in marine fishery systems - Jacob G. Eurich; Whitney R. Friedman; Kristin M. Kleisner; Lily Z. Zhao; Christopher M. Free; Meghan Fletcher; Julia G. Mason; Kanae Tokunaga; Alba Aguion; Andrea Dell'Apa; Mark Dickey‐Collas; Rod Fujita; et al. (Fish and Fisheries, 2024)
Both the ecological and social dimensions of fisheries are being affected by climate change. As a result, policymakers, managers, scientists and fishing communities are seeking guidance on how to holistically build resilience to climate change. Numerous studies have highlighted key attributes of resilience in fisheries, yet concrete examples that explicitly link these attributes to social‐ecological outcomes are lacking. To better understand climate resilience, we assembled 18 case studies spanning ecological, socio‐economic, governance and geographic contexts. Using a novel framework for evaluating 38 resilience attributes, the case studies were systematically assessed to understand how attributes enable or inhibit resilience to a given climate stressor. We found population abundance, learning capacity, and responsive governance were the most important attributes for conferring resilience, with ecosystem connectivity, place attachment, and accountable governance scoring the strongest across the climate‐resilient fisheries. We used these responses to develop an attribute typology that describes robust sources of resilience, actionable priority attributes and attributes that are case specific or require research. We identified five fishery archetypes to guide stakeholders as they set long‐term goals and prioritize actions to improve resilience. Lastly, we found evidence for two pathways to resilience: (1) building ecological assets and strengthening communities, which we observed in rural and small‐scale fisheries, and (2) building economic assets and improving effective governance, which was demonstrated in urban and wealthy fisheries. Our synthesis presents a novel framework that can be directly applied to identify approaches, pathways and actionable levers for improving climate resilience in fishery systems.

Nutricline adjustment by internal tidal beam generation enhances primary production in idealized numerical models - Jasen R. Jacobsen; Christopher A. Edwards; Brian S. Powell; John A. Colosi; Jerome Fiechter (Frontiers in Marine Science, 2023)
When the barotropic tide encounters variable bathymetry, fluctuating flow along a topographic slope generates baroclinic tides, or internal tides. There is growing evidence that these internal tides can affect primary production in the euphotic zone, though the dominant mechanisms are unclear. Internal tides move passive phytoplankton through an exponentially varying light field, enhancing primary production near the base of the euphotic zone. In addition internal tides also increase primary production through vertical nutrient advection into the euphotic zone. Topographically generated internal tides can be separated into two regimes: 1) the often highly nonlinear near-field regime where tidal beams are observed and 2) the more linear far-field regime. This study examines the primary production response to these internal tide processes using the Regional Ocean Modeling System (ROMS) coupled to a simple Nutrient, Phytoplankton, Zooplankton, Detritus (NPZD) model configured for an oligotrophic system with the nutricline positioned below 50 m depth. These idealized simulations generate internal tide beams with an oscillating, horizontal body force at the M 2 tidal frequency that is applied to domains with a bathymetric step and uniform stratification. Sensitivity of the primary production response to the energy content of the tidal beam is obtained by adjusting the height and slope of the bathymetric step. Simulation results reveal that primary production intensifies along tidal beams due to the local enhancement of parcel vertical displacement (light effect) and nutrient advective flux divergence (nutrient effect). In the near-field regime across the range of step heights and slopes in this study, the nutrient effect is an order of magnitude larger and explains 92% of the variance in primary production versus only 14% for the light effect. The geometry of the generating feature sets the kinematics of the tidal beam. The light effect is limited in the euphotic zone across our domains because realized changes in light experienced over a tidal cycle are small relative to the amount of light available at a particular depth. In contrast, the magnitude of the nutrient effect increases more substantially with tidal beam energy.

Weak constraint 4D-Var data assimilation in the Regional Ocean Modeling System (ROMS) using a saddle-point algorithm: Application to the California Current Circulation - Andrew M. Moore; Hernan G. Arango; John Wilkin; Christopher A. Edwards (Ocean Modelling, 2023)

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

Isopropyl alcohol inhalation versus 5-HT3 antagonists for treatment of nausea: a meta-analysis of randomised controlled trials - James S. Kimber; Joshua G. Kovoor; John M. Glynatsis; Samuel J. West; Thi Thien Nhi Mai; Jonathan Henry W. Jacobsen; Christopher D. Ovenden; Stephen Bacchi; Joseph N. Hewitt; Aashray K. Gupta; Suzanne Edwards; Fiona J. Taverner; et al. (European Journal of Clinical Pharmacology, 2023)
Purpose Nausea is a common and unpleasant sensation for which current therapies such as serotonin (5-HT 3 ) antagonists are often ineffective, while also conferring a risk of potential adverse events. Isopropyl alcohol (IPA) has been proposed as a treatment for nausea. We aimed to compare IPA with 5-HT 3 antagonists for the treatment of nausea across all clinical settings. Methods MEDLINE, EMBASE, PubMed, CENTRAL and CINAHL were searched from inception to 17 July 2023 for randomised controlled trials (RCTs) comparing inhaled IPA and a 5-HT 3 antagonist for treatment of nausea. Severity and duration of nausea, rescue antiemetic use, adverse events and patient satisfaction were the outcomes sought. Risk of bias (RoB) was assessed using Cochrane RoB 2. Random-effects model was used for meta-analysis. Combination of meta-analyses and narrative review was used to synthesise findings. The evidence was appraised using GRADE. Results From 1242 records, 4 RCTs were included with 382 participants. Participants receiving IPA had a significantly lower mean time to 50% reduction in nausea (MD − 20.06; 95% CI − 26.26, − 13.85). Nausea score reduction at 30 min was significantly greater in the IPA group (MD 21.47; 95% CI 15.47, 27.47). IPA led to significantly reduced requirement for rescue antiemetics (OR 0.60; 95% CI 0.37, 0.95; p = 0.03). IPA led to no significant difference in patient satisfaction when compared with a 5-HT 3 antagonist. The overall GRADE assessment of evidence quality ranged from very low to low. Conclusion IPA may provide rapid, effective relief of nausea when compared with 5-HT 3 antagonists.

Evaluating Alternate Methods of 4D-Var Data Assimilation in a Coupled Hydrodynamic—Four-Component Biogeochemical Model of the California Current System - Jonathan G. Izett; J. Paul Mattern; Andrew M. Moore; Christopher A. Edwards (Ocean Modelling, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Sequence Divergence in Venom Genes Within and Between Montane Pitviper (Viperidae: Crotalinae: Cerrophidion) Species is Driven by Mutation–Drift Equilibrium - Ramses Alejandro Rosales-García; Rhett M. Rautsaw; Erich P. Hofmann; Christoph I. Grünwald; Hector Franz-Chavez; Ivan T. Ahumada-Carrillo; Ricardo Ramirez-Chaparro; Miguel Angel de la Torre-Loranca; Jason L. Strickland; Andrew J. Mason; Matthew L. Holding; Miguel Borja; et al. (Journal of Molecular Evolution, 2023)

Modeling the dispersal of the San Francisco Bay plume over the northern and central California shelf - Jian Zhou; Jonathan G. Izett; Christopher A. Edwards; Pierre Damien; Fayçal Kessouri; James C. McWilliams (Estuarine, Coastal and Shelf Science, 2023)

Rapidly Changing Range Limits in a Warming World: Critical Data Limitations and Knowledge Gaps for Advancing Understanding of Mangrove Range Dynamics in the Southeastern USA - Rémi Bardou; Michael J. Osland; Steven Scyphers; Christine Shepard; Karen E. Aerni; Jahson B. Alemu I; Robert Crimian; Richard H. Day; Nicholas M. Enwright; Laura C. Feher; Sarah L. Gibbs; Kiera O’Donnell; et al. (Estuaries and Coasts, 2023)
Climate change is altering species’ range limits and transforming ecosystems. For example, warming temperatures are leading to the range expansion of tropical, cold-sensitive species at the expense of their cold-tolerant counterparts. In some temperate and subtropical coastal wetlands, warming winters are enabling mangrove forest encroachment into salt marsh, which is a major regime shift that has significant ecological and societal ramifications. Here, we synthesized existing data and expert knowledge to assess the distribution of mangroves near rapidly changing range limits in the southeastern USA. We used expert elicitation to identify data limitations and highlight knowledge gaps for advancing understanding of past, current, and future range dynamics. Mangroves near poleward range limits are often shorter, wider, and more shrublike compared to their tropical counterparts that grow as tall forests in freeze-free, resource-rich environments. The northern range limits of mangroves in the southeastern USA are particularly dynamic and climate sensitive due to abundance of suitable coastal wetland habitat and the exposure of mangroves to winter temperature extremes that are much colder than comparable range limits on other continents. Thus, there is need for methodological refinements and improved spatiotemporal data regarding changes in mangrove structure and abundance near northern range limits in the southeastern USA. Advancing understanding of rapidly changing range limits is critical for foundation plant species such as mangroves, as it provides a basis for anticipating and preparing for the cascading effects of climate-induced species redistribution on ecosystems and the human communities that depend on their ecosystem services.

Aquatic insect accumulation of uranium at spring outflows in the Grand Canyon region as influenced by aqueous and sediment geochemistry and biological factors: implications for monitoring - Daniel J. Cain; Marie-Noële Croteau; Christopher C. Fuller; Kimberly R. Beisner; Kate M. Campbell; Deborah L. Stoliker; Edward R. Schenk (Environmental Monitoring and Assessment, 2023)

Coral adaptive capacity insufficient to halt global transition of coral reefs into net erosion under climate change - Christopher Edward Cornwall; Steeve Comeau; Simon D. Donner; Chris Perry; John Dunne; Ruben van Hooidonk; James S. Ryan; Cheryl A. Logan (Global Change Biology, 2023)
Projecting the effects of climate change on net reef calcium carbonate production is critical to understanding the future impacts on ecosystem function, but prior estimates have not included corals' natural adaptive capacity to such change. Here we estimate how the ability of symbionts to evolve tolerance to heat stress, or for coral hosts to shuffle to favourable symbionts, and their combination, may influence responses to the combined impacts of ocean warming and acidification under three representative concentration pathway (RCP) emissions scenarios (RCP2.6, RCP4.5 and RCP8.5). We show that symbiont evolution and shuffling, both individually and when combined, favours persistent positive net reef calcium carbonate production. However, our projections of future net calcium carbonate production (NCCP) under climate change vary both spatially and by RCP. For example, 19%–35% of modelled coral reefs are still projected to have net positive NCCP by 2050 if symbionts can evolve increased thermal tolerance, depending on the RCP. Without symbiont adaptive capacity, the number of coral reefs with positive NCCP drops to 9%–13% by 2050. Accounting for both symbiont evolution and shuffling, we project median positive NCPP of coral reefs will still occur under low greenhouse emissions (RCP2.6) in the Indian Ocean, and even under moderate emissions (RCP4.5) in the Pacific Ocean. However, adaptive capacity will be insufficient to halt the transition of coral reefs globally into erosion by 2050 under severe emissions scenarios (RCP8.5).

Improving the combined use of reflectance and thermal channels for ocean and coastal cloud detection for the Sea and Land Surface Temperature Radiometer (SLSTR) - Claire E. Bulgin; Agnieszka Faulkner; Christopher J. Merchant; Gary K. Corlett; Niall McCarroll; Owen Embury; Edward Polehampton; Connor McGurk (Remote Sensing of Environment, 2023)

Targeting Redundant ROBO1 and SDF-1 Pathways Prevents Adult Hemangioblast Derived-EPC and CEC Activity Effectively Blocking Tumor Neovascularization - Anitha K. Shenoy; Liya Pi; Alexander P. Ligocki; Koji Hosaka; Christopher R. Cogle; Edward W. Scott (Stem Cell Reviews and Reports, 2023)

Forecast Sensitivity-based Observation Impact (FSOI) in an analysis–forecast system of the California Current Circulation - Patrick Drake; Christopher A. Edwards; Hernan G. Arango; John Wilkin; Tayebeh TajalliBakhsh; Brian Powell; Andrew M. Moore (Ocean Modelling, 2023)

Climate-driven shifts in pelagic fish distributions in a rapidly changing Pacific Arctic - Robert M. Levine; Alex De Robertis; Daniel Grünbaum; Sharon Wildes; Edward V. Farley; Phyllis J. Stabeno; Christopher D. Wilson (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Investigation of the Readability and Reliability of Online Health Information for Cancer Patients During the Coronavirus Pandemic - Cameron Schluter; Maia Fefer; Grace Lee; Isaac G. Alty; Edward Christopher Dee (Journal of Cancer Education, 2023)

Dilated hypertrophic phenotype of the carotid artery is associated with accelerated age-associated central arterial stiffening - Majd AlGhatrif; Edward G. Lakatta; Christopher H. Morrell; Danilo Alunni Fegatelli; Edoardo Fiorillo; Michele Marongiu; David Schlessinger; Francesco Cucca; Angelo Scuteri (GeroScience, 2023)

Detection of numerous phycotoxins in young bull sharks (Carcharhinus leucas) collected from an estuary of national significance - Michelle L. Edwards; Adam M. Schaefer; Malcolm McFarland; Spencer Fire; Christopher R. Perkins; Matthew J. Ajemian (Science of The Total Environment, 2023)

Lava-ice interactions during historical eruptions of Veniaminof Volcano, Alaska and the potential for meltwater floods and lahars - Christopher F. Waythomas; Benjamin R. Edwards; Thomas P. Miller; Robert G. McGimsey (Natural Hazards, 2023)
Veniaminof Volcano on the Alaska Peninsula of southwest Alaska is one of a small group of ice-clad volcanoes globally that erupts lava flows in the presence of glacier ice. Here, we describe the nature of lava-ice-snow interactions that have occurred during historical eruptions of the volcano since 1944. Lava flows with total volumes on the order of 0.006 km 3 have been erupted in 1983–1984, 1993–1994, 2013, and 2018. Smaller amounts of lava (1 × 10 −4 km 3 or less) were generated during eruptions in 1944 and 2021. All known historical eruptions have occurred at a 300-m-high cinder cone (informally named cone A) within the 8 × 10-km-diameter ice-filled caldera that characterizes Veniaminof Volcano. Supraglacial lava flows erupted at cone A, resulted in minor amounts of melting and did not lead to any significant outflows of water in nearby drainages. Subglacial effusion of lava in 1983–1984, 2021 and possibly in 1944 and 1993–1994 resulted in more significant melting including a partially water-filled melt pit, about 0.8 km 2 in area, that developed during the 1983–1984 eruption. The 1983–1984 event created an impression that meltwater floods from Mount Veniaminof’s ice-filled caldera could be significant and hazardous given the large amount of glacier ice resident within the caldera (ice volume about 8 km 3 ). To date, no evidence supporting catastrophic outflow of meltwater from lava-ice interactions at cone A has been found. Analysis of imagery from the 1983–1984 eruption shows that the initial phase erupted englacial lavas that melted ice/snow/firn from below, producing surface subsidence outward from the cone with no discernable surface connection to the summit vent on cone A. This also happened during the 2021 eruption, and possibly during the 1993–1994 eruption although meltwater lakes did not form during these events. Thus, historical eruptions at Veniaminof Volcano appear to have two different modes of effusive eruptive behavior, where lava reaches the ice subglacially from flank vents, or where lava flows are erupted subaerially from vents near the summit of cone A and flow down the cone on to the ice surface. When placed in the context of global lava-ice eruptions, in cases where lava flows melt the ice from the surface downward, the main hazards are from localized phreatic explosions as opposed to potential flood/lahar hazards. However, when lava effusion/emplacement occurs beneath the ice surface, melting is more rapid and can produce lakes whose drainage could plausibly produce localized floods and lahars.

Emergence of heartbeat frailty in advanced age I: perspectives from life-long EKG recordings in adult mice - Jack M. Moen; Christopher H. Morrell; Michael G. Matt; Ismayil Ahmet; Syevda Tagirova; Moran Davoodi; Michael Petr; Shaquille Charles; Rafael de Cabo; Yael Yaniv; Edward G. Lakatta (GeroScience, 2022)
The combined influences of sinoatrial nodal (SAN) pacemaker cell automaticity and its response to autonomic input determine the heart’s beating interval variability and mean beating rate. To determine the intrinsic SAN and autonomic signatures buried within EKG RR interval time series change in advanced age, we measured RR interval variability before and during double autonomic blockade at 3-month intervals from 6 months of age until the end of life in long-lived (those that achieved the total cohort median life span of 24 months and beyond) C57/BL6 mice. Prior to 21 months of age, time-dependent changes in intrinsic RR interval variability and mean RR interval were relatively minor. Between 21 and 30 months of age, however, marked changes emerged in intrinsic SAN RR interval variability signatures, pointing to a reduction in the kinetics of pacemaker clock mechanisms, leading to reduced synchronization of molecular functions within and among SAN cells. This loss of high-frequency signal processing within intrinsic SAN signatures resulted in a marked increase in the mean intrinsic RR interval. The impact of autonomic signatures on RR interval variability were net sympathetic and partially compensated for the reduced kinetics of the intrinsic SAN RR interval variability signatures, and partially, but not completely, shifted the EKG RR time series intervals to a more youthful pattern. Cross-sectional analyses of other subsets of C57/BL6 ages indicated that at or beyond the median life span of our longitudinal cohort, noncardiac, constitutional, whole-body frailty was increased, energetic efficiency was reduced, and the respiratory exchange ratio increased. We interpret the progressive reduction in kinetics in intrinsic SAN RR interval variability signatures in this context of whole-body frailty beyond 21 months of age to be a manifestation of “heartbeat frailty.”

Memory rehabilitation: restorative, specific knowledge acquisition, compensatory, and holistic approaches - Yashoda Gopi; Edward Wilding; Christopher R. Madan (Cognitive Processing, 2022)
Memory impairment following an acquired brain injury can negatively impact daily living and quality of life—but can be reduced by memory rehabilitation. Here, we review the literature on four approaches for memory rehabilitation and their associated strategies: (1) the restorative approach, aimed at a return to pre-morbid functioning, (2) the knowledge acquisition approach, involving training on specific information relevant to daily life, (3) the compensatory approach, targeted at improving daily functioning, and (4) the holistic approach, in which social, emotional, and behavioral deficits are addressed alongside cognitive consequences of acquired brain injury. Each memory rehabilitation approach includes specific strategies such as drill and practice (restorative), spaced retrieval (knowledge acquisition), memory aids (compensatory), or a combination of psychotherapy and cognitive strategies (holistic). Past research has demonstrated mixed support for the use of restorative strategies to improve memory function, whereas knowledge acquisition strategies show promising results on trained tasks but little generalization to untrained tasks and activities of daily living. Compensatory strategies remain widely used but require intensive training to be effectively employed. Finally, the holistic approach is becoming more widespread due to improvements in psychosocial wellbeing, yet there are considerable resource and cost requirements. Several factors can influence rehabilitation outcomes including metacognition and emotional disturbances. Considerations for future research to improve the applicability of strategies for memory rehabilitation include assessing memory impairment severity, examining memory needs in daily life, and exploring the long-term effects of memory rehabilitation.

Comparison of Three Automated Approaches for Classification of Amyloid-PET Images - Ying-Hwey Nai; Yee-Hsin Tay; Tomotaka Tanaka; Christopher P. Chen; Edward G. Robins; Anthonin Reilhac (Neuroinformatics, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Cancer clinical trials in the Philippines - Michelle Ann B. Eala; Patricia Anne S. Basilio; Edward Christopher Dee; Reno Eufemon P. Cereno; Christian Daniel Ang; Nikko J. Magsanoc; Frederic Ivan L. Ting; Dennis L. Sacdalan (Cancer Causes & Control, 2022)

Subarctic soil carbon losses after deforestation for agriculture depend on permafrost abundance - Tino Peplau; Julia Schroeder; Edward Gregorich; Christopher Poeplau (Global Change Biology, 2022)
The northern circumpolar permafrost region is experiencing considerable warming due to climate change, which is allowing agricultural production to expand into regions of discontinuous and continuous permafrost. The conversion of forests to arable land might further enhance permafrost thaw and affect soil organic carbon (SOC) that had previously been protected by frozen ground. The interactive effect of permafrost abundance and deforestation on SOC stocks has hardly been studied. In this study, soils were sampled on 18 farms across the Yukon on permafrost and non‐permafrost soils to quantify the impact of land‐use change from forest to cropland and grassland on SOC stocks. Furthermore, the soils were physically and chemically fractionated to assess the impact of land‐use change on different functional pools of SOC. On average, permafrost‐affected forest soils lost 15.6 ± 21.3% of SOC when converted to cropland and 23.0 ± 13.0% when converted to grassland. No permafrost was detected in the deforested soils, indicating that land‐use change strongly enhanced warming and subsequent thawing. In contrast, the change in SOC at sites without permafrost was not significant but had a slight tendency to be positive. SOC stocks were generally lower at sites without permafrost under forest. Furthermore, land‐use change increased mineral‐associated SOC, while the fate of particulate organic matter (POM) after land‐use change depended on permafrost occurrence. Permafrost soils showed significant POM losses after land‐use change, while grassland sites without permafrost gained POM in the topsoil. The results showed that the fate of SOC after land‐use change greatly depended on the abundance of permafrost in the pristine forest, which was driven by climatic conditions more than by soil properties. It can be concluded that in regions of discontinuous permafrost in particular, initial conditions in forest soils should be considered before deforestation to minimize its climate impact.

A New Insight Into Amicula, a Genus of Tiny Marine Benthic Diatoms With the Description of Two New Tropical Species and the Largest Mitogenome Known for a Stramenopile - Romain Gastineau; Chunlian Li; Matt P. Ashworth; Andrzej Witkowski; Monique Turmel; Ewa Górecka; Thomas A. Frankovich; Anna Wachnicka; Christopher S. Lobban; Edward C. Theriot; Christian Otis; Przemysław Dąbek; et al. (Frontiers in Marine Science, 2022)
The current article focuses on the morphological and molecular characterization of the often inconspicuous genus Amicula. This recently erected genus from brackish and marine sediments was monotypic but here we describe two new tropical species: Amicula micronesica sp. nov. and Amicula vermiculata sp. nov. Once considered an incertae sedis genus regarding its higher rank taxonomy, its position among the family Diploneidaceae is proposed here by molecular phylogenetics. The complete plastid and mitochondrial genomes of Amicula micronesica sp. nov. are also presented here. It appears that the 177614-bp long mitogenome is the biggest yet recorded among stramenopiles, due to its invasion by 57 introns. Moreover, it utilizes the genetic code 4 for translation instead of the code 1 usually found among diatoms.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Wildfire, Smoke Exposure, Human Health, and Environmental Justice Need to be Integrated into Forest Restoration and Management - Savannah M. D’Evelyn; Jihoon Jung; Ernesto Alvarado; Jill Baumgartner; Pete Caligiuri; R. Keala Hagmann; Sarah B. Henderson; Paul F. Hessburg; Sean Hopkins; Edward J. Kasner; Meg A. Krawchuk; Jennifer E. Krenz; et al. (Current Environmental Health Reports, 2022)
Purpose of Review Increasing wildfire size and severity across the western United States has created an environmental and social crisis that must be approached from a transdisciplinary perspective. Climate change and more than a century of fire exclusion and wildfire suppression have led to contemporary wildfires with more severe environmental impacts and human smoke exposure. Wildfires increase smoke exposure for broad swaths of the US population, though outdoor workers and socially disadvantaged groups with limited adaptive capacity can be disproportionally exposed. Exposure to wildfire smoke is associated with a range of health impacts in children and adults, including exacerbation of existing respiratory diseases such as asthma and chronic obstructive pulmonary disease, worse birth outcomes, and cardiovascular events. Seasonally dry forests in Washington, Oregon, and California can benefit from ecological restoration as a way to adapt forests to climate change and reduce smoke impacts on affected communities. Recent Findings Each wildfire season, large smoke events, and their adverse impacts on human health receive considerable attention from both the public and policymakers. The severity of recent wildfire seasons has state and federal governments outlining budgets and prioritizing policies to combat the worsening crisis. This surging attention provides an opportunity to outline the actions needed now to advance research and practice on conservation, economic, environmental justice, and public health interests, as well as the trade-offs that must be considered. Summary Scientists, planners, foresters and fire managers, fire safety, air quality, and public health practitioners must collaboratively work together. This article is the result of a series of transdisciplinary conversations to find common ground and subsequently provide a holistic view of how forest and fire management intersect with human health through the impacts of smoke and articulate the need for an integrated approach to both planning and practice.

Estimated life-history traits and movements of the Caribbean reef shark (Carcharhinus perezi) in The Bahamas based on tag-recapture data - Brendan S. Talwar; Darcy Bradley; Christopher Berry; Mark E. Bond; Ian A. Bouyoucos; Annabelle M. L. Brooks; Candace Y. A. Fields; Austin J. Gallagher; Tristan L. Guttridge; Annie E. Guttridge; Neil Hammerschlag; Ian Hamilton; et al. (Marine Biology, 2022)

Transport Processes in the Gulf of Mexico Along the River-Estuary-Shelf-Ocean Continuum: a Review of Research from the Gulf of Mexico Research Initiative - Dubravko Justić; Villy Kourafalou; Giulio Mariotti; Songjie He; Robert Weisberg; Yannis Androulidakis; Christopher Barker; Annalisa Bracco; Brian Dzwonkowski; Chuanmin Hu; Haosheng Huang; Gregg Jacobs; et al. (Estuaries and Coasts, 2022)
Estuarine and coastal geomorphology, biogeochemistry, water quality, and coastal food webs in river-dominated shelves of the Gulf of Mexico (GoM) are modulated by transport processes associated with river inputs, winds, waves, tides, and deep-ocean/continental shelf interactions. For instance, transport processes control the fate of river-borne sediments, which in turn affect coastal land loss. Similarly, transport of freshwater, nutrients, and carbon control the dynamics of eutrophication, hypoxia, harmful algal blooms, and coastal acidification. Further, freshwater inflow transports pesticides, herbicides, heavy metals, and oil into receiving estuaries and coastal systems. Lastly, transport processes along the continuum from the rivers and estuaries to coastal and shelf areas and adjacent open ocean (abbreviated herein as “river-estuary-shelf-ocean”) regulate the movements of organisms, including the spatial distributions of individuals and the exchange of genetic information between distinct subpopulations. The Gulf of Mexico Research Initiative (GoMRI) provided unprecedented opportunities to study transport processes along the river-estuary-shelf-ocean continuum in the GoM. The understanding of transport at multiple spatial and temporal scales in this topographically and dynamically complex marginal sea was improved, allowing for more accurate forecasting of the fate of oil and other constituents. For this review, we focus on five specific transport themes: (i) wetland, estuary, and shelf exchanges; (ii) river-estuary coupling; (iii) nearshore and inlet processes; (iv) open ocean transport processes; and (v) river-induced fronts and cross-basin transport. We then discuss the relevancy of GoMRI findings on the transport processes for ecological connectivity and oil transport and fate. We also examine the implications of new findings for informing the response to future oil spills, and the management of coastal resources and ecosystems. Lastly, we summarize the research gaps identified in the many studies and offer recommendations for continuing the momentum of the research provided by the GoMRI effort. A number of uncertainties were identified that occurred in multiple settings. These include the quantification of sediment, carbon, dissolved gasses and nutrient fluxes during storms, consistent specification of the various external forcings used in analyses, methods for smooth integration of multiscale advection mechanisms across different flow regimes, dynamic coupling of the atmosphere with sub-mesoscale and mesoscale phenomena, and methods for simulating finer-scale dynamics over long time periods. Addressing these uncertainties would allow the scientific community to be better prepared to predict the fate of hydrocarbons and their impacts to the coastal ocean, rivers, and marshes in the event of another spill in the GoM.

Development of duplex qPCR targeting Carnobacterium maltaromaticum and Vagococcus salmoninarum - Isaac Standish; Rebekah McCann; Corey Puzach; Eric Leis; Jennifer Bailey; Sara Dziki; Ryan Katona; Ellen Lark; Carey Edwards; Brandon Keesler; Stephen Reichley; Stacy King; et al. (Journal of Fish Diseases, 2022)
In November 2018, Vagococcus salmoninarum was identified as the causative agent of a chronic coldwater streptococcosis epizootic in broodstock brook trout ( Salvelinus fontinalis ) at the Iron River National Fish Hatchery in Wisconsin, USA. By February 2019, the epizootic spread to adjacent raceways containing broodstock lake trout ( Salvelinus namaycush ), whereby fish were found to be coinfected with Carnobacterium maltaromaticum and V . salmoninarum . To differentiate these two pathogens and determine the primary cause of the lake trout morbidity, a quantitative real‐time PCR (qPCR) was developed targeting the C . maltaromaticum phenylalanyl‐tRNA synthase alpha subunit ( pheS ) gene. The qPCR was combined with a V . salmoninarum qPCR, creating a duplex qPCR assay that simultaneously quantitates C. maltaromaticum and V . salmoninarum concentrations in individual lake trout tissues, and screens presumptive isolates from hatchery inspections and wild fish from national fish hatchery source waters throughout the Great Lakes basin. Vagococcus salmoninarum and C. maltaromaticum were co‐detected in broodstock brook trout from two tribal hatcheries and C. maltaromaticum was present in wild fish in source waters of several national fish hatcheries. This study provides a powerful new tool to differentiate and diagnose two emerging Gram‐positive bacterial pathogens.

Attributes of climate resilience in fisheries: From theory to practice - Julia G. Mason; Jacob G. Eurich; Jacqueline D. Lau; Willow Battista; Christopher M. Free; Katherine E. Mills; Kanae Tokunaga; Lily Z. Zhao; Mark Dickey‐Collas; Mireia Valle; Gretta T. Pecl; Joshua E. Cinner; et al. (Fish and Fisheries, 2022)
In a changing climate, there is an imperative to build coupled social‐ecological systems—including fisheries—that can withstand or adapt to climate stressors. Although resilience theory identifies system attributes that supposedly confer resilience, these attributes have rarely been clearly defined, mechanistically explained, nor tested and applied to inform fisheries governance. Here, we develop and apply a comprehensive resilience framework to examine fishery systems across (a) ecological, (b) socio‐economic and (c) governance dimensions using five resilience domains: assets, flexibility, organization, learning and agency. We distil and define 38 attributes that confer climate resilience from a coupled literature‐ and expert‐driven approach, describe how they apply to fisheries and provide illustrative examples of resilience attributes in action. Our synthesis highlights that the directionality and mechanism of these attributes depend on the specific context, capacities, and scale of the focal fishery system and associated stressors, and we find evidence of interdependencies among attributes. Overall, however, we find few studies that test resilience attributes in fisheries across all parts of the system, with most examples focussing on the ecological dimension. As such, meaningful quantification of the attributes’ contributions to resilience remains a challenge. Our synthesis and holistic framework represent a starting point for critical application of resilience concepts to fisheries social‐ecological systems.

Importance of equitable cost sharing in the Convention on Biological Diversity's protected area agenda - Keila Stark; Vanessa Adams; Christopher J. Brown; Alienor Chauvenet; Katrina Davis; Edward T. Game; Benjamin S. Halpern; John Lynham; Bonnie Mappin; Kim Selkoe; James E. M. Watson; Hugh P. Possingham; et al. (Conservation Biology, 2022)

Global biogeographic patterns of avian morphological diversity - Emma C. Hughes; David P. Edwards; Jen A. Bright; Elliot J.R. Capp; Christopher R. Cooney; Zoë K. Varley; Gavin H. Thomas (Ecology Letters, 2022)
Understanding the biogeographical patterns, and evolutionary and environmental drivers, underpinning morphological diversity are key for determining its origins and conservation. Using a comprehensive set of continuous morphological traits extracted from museum collections of 8353 bird species, including geometric morphometric beak shape data, we find that avian morphological diversity is unevenly distributed globally, even after controlling for species richness, with exceptionally dense packing of species in hyper‐diverse tropical hotspots. At the regional level, these areas also have high morphological variance, with species exhibiting high phenotypic diversity. Evolutionary history likely plays a key role in shaping these patterns, with evolutionarily old species contributing to niche expansion, and young species contributing to niche packing. Taken together, these results imply that the tropics are both ‘cradles’ and ‘museums’ of phenotypic diversity.

Persistently elevated complement alternative pathway biomarkers in COVID-19 correlate with hypoxemia and predict in-hospital mortality - Alexander Leatherdale; Sophie Stukas; Victor Lei; Henry E. West; Christopher J. Campbell; Ryan L. Hoiland; Jennifer Cooper; Cheryl L. Wellington; Mypinder S. Sekhon; Edward L. G. Pryzdial; Edward M. Conway (Medical Microbiology and Immunology, 2022)

Observation of Aerosol Generation by Human Subjects During Cardiopulmonary Exercise Testing Using a High-Powered Laser Technique: A Pilot Project - Christopher M. Varga; Keith J. Kwiatkowski; Michael J. Pedro; Herman Groepenhoff; Edward A. Rose; Callum Gray; Kai D. Pinkerton; Michael G. McBride; Stephen M. Paridon (Journal of Medical and Biological Engineering, 2022)

A National-Level Assessment of Lemur Hunting Pressure in Madagascar - Cortni Borgerson; Steig E. Johnson; Emma Hall; Kerry A. Brown; Pamela R. Narváez-Torres; Be Jean Rodolph Rasolofoniaina; Be Noel Razafindrapaoly; Samuel D. Merson; Katharine E. T. Thompson; Sheila M. Holmes; Edward E. Louis; Christopher D. Golden (International Journal of Primatology, 2022)

Contrasting climate velocity impacts in warm and cool locations show that effects of marine warming are worse in already warmer temperate waters - Philina A. English; Eric J. Ward; Christopher N. Rooper; Robyn E. Forrest; Luke A. Rogers; Karen L. Hunter; Andrew M. Edwards; Brendan M. Connors; Sean C. Anderson (Fish and Fisheries, 2022)
Species responses to climate change are often measured at broad spatiotemporal scales, which can miss the fine‐scale changes that are most relevant to conservation and fisheries management. We develop a scaleable geostatistical approach to assess how juvenile and adult fish distributions have been shaped by changes in bottom temperature and dissolved oxygen over a recent decade of warming in the northeast Pacific. Across 38 demersal fishes, biomass trends were associated negatively with warming and positively with dissolved oxygen, but when trends in both biomass and climate were converted to velocities—the speed and direction a population would have to move to maintain consistent conditions—the effect of temperature change differed depending on local conditions. In the warmest locations, warming velocities were associated with negative biotic velocities for 19 of 69 species‐maturity combinations, and yet were almost always associated with stable or positive biotic velocities in the coolest locations (64 of 69). These spatially consistent biomass declines (negative biotic velocities) in the warmest locations and increases in cooler locations suggest a redistribution of species with the potential for new ecological and fisheries interactions. After controlling for temperature, the more spatially consistent effects of dissolved oxygen were often negative, suggesting a mechanism other than hypoxia avoidance—potentially changes in primary production. Our approach identifies the species and locations that are most sensitive to observed changes in the environment at any scale, thus facilitating future vulnerability assessments.

Bladder Cancer and Google Trends: Associations Between US Search Patterns and Disease Outcomes May Show Need for Improved Awareness Strategies - Joseph Alexander Paguio; Jasper Seth Yao; Ma. Sophia Graciela L. Reyes; Grace Lee; Edward Christopher Dee (Journal of Cancer Education, 2021)

Long‐term geothermal warming reduced stocks of carbon but not nitrogen in a subarctic forest soil - Tino Peplau; Julia Schroeder; Edward Gregorich; Christopher Poeplau (Global Change Biology, 2021)
Global warming is accelerating the decomposition of soil organic matter (SOM). When predicting the net SOM dynamics in response to warming, there are considerable uncertainties owing to experimental limitations. Long‐term in situ whole‐profile soil warming studies are particularly rare. This study used a long‐term, naturally occurring geothermal gradient in Yukon, Canada, to investigate the warming effects on SOM in a forest ecosystem. Soils were sampled along this thermosequence which exhibited warming of up to 7.7℃; samples were collected to a depth of 80 cm and analysed for soil organic carbon (SOC) and nitrogen (N) content, and estimates made of SOC stock and fractions. Potential litter decomposition rates as a function of soil temperature and depth were observed for a 1‐year period using buried teabags and temperature loggers. The SOC in the topsoil (0–20 cm) and subsoil (20–80 cm) responded similar to warming. A negative relationship was found between soil temperature and whole‐profile SOC stocks, with a total loss of 27% between the warmest and reference plots, and a relative loss of 3%℃ −1 . SOC losses were restricted to the particulate organic matter (POM) and dissolved organic carbon (DOC) fractions with net whole‐profile depletions. Losses in POM‐C accounted for the largest share of the total SOC losses. In contrast to SOC, N was not lost from the soil as a result of warming, but was redistributed with a relatively large accumulation in the silt and clay fraction (+40%). This suggests an immobilization of N by microbes building up in mineral‐associated organic matter. These results confirm that soil warming accelerates SOC turnover throughout the profile and C is lost in both the topsoil and subsoil. Since N stocks remained constant with warming, SOM stoichiometry changed considerably and this in turn could affect C cycling through changes in microbial metabolism.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Environmental Drivers of Forage Fishes and Benthic Invertebrates at Multiple Spatial Scales in a Large Temperate Estuary - Ryan J. Woodland; Andre Buchheister; Robert J. Latour; Carlos Lozano; Edward Houde; Christopher J. Sweetman; Mary C. Fabrizio; Troy D. Tuckey (Estuaries and Coasts, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Recognize fish as food in policy discourse and development funding - Abigail Bennett; Xavier Basurto; John Virdin; Xinyan Lin; Samantha J. Betances; Martin D. Smith; Edward H. Allison; Barbara A. Best; Kelly D. Brownell; Lisa M. Campbell; Christopher D. Golden; Elizabeth Havice; et al. (Ambio, 2021)
The international development community is off-track from meeting targets for alleviating global malnutrition. Meanwhile, there is growing consensus across scientific disciplines that fish plays a crucial role in food and nutrition security. However, this ‘fish as food’ perspective has yet to translate into policy and development funding priorities. We argue that the traditional framing of fish as a natural resource emphasizes economic development and biodiversity conservation objectives, whereas situating fish within a food systems perspective can lead to innovative policies and investments that promote nutrition-sensitive and socially equitable capture fisheries and aquaculture. This paper highlights four pillars of research needs and policy directions toward this end. Ultimately, recognizing and working to enhance the role of fish in alleviating hunger and malnutrition can provide an additional long-term development incentive, beyond revenue generation and biodiversity conservation, for governments, international development organizations, and society more broadly to invest in the sustainability of capture fisheries and aquaculture.

Differences in microbial community response to nitrogen fertilization result in unique enzyme shifts between arbuscular and ectomycorrhizal‐dominated soils - Joseph E. Carrara; Christopher A. Walter; Zachary B. Freedman; Ashley N. Hostetler; Jennifer S. Hawkins; Ivan J. Fernandez; Edward R. Brzostek (Global Change Biology, 2021)
While the effect of nitrogen (N) deposition on belowground carbon (C) cycling varies, emerging evidence shows that forest soils dominated by trees that associate with ectomycorrhizal fungi (ECM) store more C than soils dominated by trees that associate with arbuscular mycorrhizae (AM) with increasing N deposition. We hypothesized that this is due to unique nutrient cycling responses to N between AM and ECM‐dominated soils. ECM trees primarily obtain N through fungal mining of soil organic matter subsidized by root‐C. As such, we expected the largest N‐induced responses of C and N cycling to occur in ECM rhizospheres and be driven by fungi. Conversely, as AM trees rely on bacterial scavengers in bulk soils to cycle N, we predicted the largest AM responses to be driven by shifts in bacteria and occur in bulk soils. To test this hypothesis, we measured microbial community composition, metatranscriptome profiles, and extracellular enzyme activity in bulk, rhizosphere, and organic horizon (OH) soils in AM and ECM‐dominated soils at Bear Brook Watershed in Maine, USA. After 27 years of N fertilization, fungal community composition shifted across ECM soils, but bacterial communities shifted across AM soils. These shifts were mirrored by enhanced C relative to N mining enzyme activities in both mycorrhizal types, but this occurred in different soil fractions. In ECM stands these shifts occurred in rhizosphere soils, but in AM stands they occurred in bulk soils. Additionally, ECM OH soils exhibited the opposite response with declines in C relative to N mining. As rhizosphere soils account for only a small portion of total soil volume relative to bulk soils, coupled with declines in C to N enzyme activity in ECM OH soils, we posit that this may partly explain why ECM soils store more C than AM soils as N inputs increase.

The Impact of Wave Model Source Terms and Coupling Strategies to Rapidly Developing Waves across the North-West European Shelf during Extreme Events - Nieves G. Valiente; Andrew Saulter; John M. Edwards; Huw W. Lewis; Juan M. Castillo Sanchez; Diego Bruciaferri; Christopher Bunney; John Siddorn (Journal of Marine Science and Engineering, 2021)
Prediction of severe natural hazards requires accurate forecasting systems. Recently, there has been a tendency towards more integrated solutions, where different components of the Earth system are coupled to explicitly represent the physical feedbacks between them. This study focuses on rapidly developing waves under extratropical storms to understand the impact of different wave source term parameterisations in the WAVEWATCH III (WWIII) model (ST4 and ST6) and coupling strategies (surface roughness closure versus surface stress closure) on the accuracy of the Met Office regional atmosphere-ocean-wave coupled research system for the north-west (NW) European shelf (UKC4). Results of a study focused on simulations during winter 2013/14 demonstrate that ST6 allows for a faster wave growth than the ST4 parameterisation but might degrade low to mid energy wave states. The difference between ST6 and ST4 in wave growth is larger for higher wind speeds and short fetches. The experiment with ST4 and roughness closure consistently under-predicts the wave growth in those locations where fetch dependence is an important factor (i.e., seas at the East (E) of Ireland and the UK for storms coming from the NW-WNW). The implementation in the wave model of ST6 physics with the stress closure coupling strategy appears to improve growth of young wind-seas, reducing bias in those locations where the storms are underestimated. The slower wave growth when using surface roughness closure seems to be related to an underestimation of the momentum transfer computed by the wave model when coupling the wind speeds. For very young to young wind seas, this can be overcome when the surface stress is computed by the atmospheric model and directly passed to the ocean.

A Dynamically Downscaled Ensemble of Future Projections for the California Current System - Mercedes Pozo Buil; Michael G. Jacox; Jerome Fiechter; Michael A. Alexander; Steven J. Bograd; Enrique N. Curchitser; Christopher A. Edwards; Ryan R. Rykaczewski; Charles A. Stock (Frontiers in Marine Science, 2021)
Given the ecological and economic importance of eastern boundary upwelling systems like the California Current System (CCS), their evolution under climate change is of considerable interest for resource management. However, the spatial resolution of global earth system models (ESMs) is typically too coarse to properly resolve coastal winds and upwelling dynamics that are key to structuring these ecosystems. Here we use a high-resolution (0.1°) regional ocean circulation model coupled with a biogeochemical model to dynamically downscale ESMs and produce climate projections for the CCS under the high emission scenario, Representative Concentration Pathway 8.5. To capture model uncertainty in the projections, we downscale three ESMs: GFDL-ESM2M, HadGEM2-ES, and IPSL-CM5A-MR, which span the CMIP5 range for future changes in both the mean and variance of physical and biogeochemical CCS properties. The forcing of the regional ocean model is constructed with a “time-varying delta” method, which removes the mean bias of the ESM forcing and resolves the full transient ocean response from 1980 to 2100. We found that all models agree in the direction of the future change in offshore waters: an intensification of upwelling favorable winds in the northern CCS, an overall surface warming, and an enrichment of nitrate and corresponding decrease in dissolved oxygen below the surface mixed layer. However, differences in projections of these properties arise in the coastal region, producing different responses of the future biogeochemical variables. Two of the models display an increase of surface chlorophyll in the northern CCS, consistent with a combination of higher nitrate content in source waters and an intensification of upwelling favorable winds. All three models display a decrease of chlorophyll in the southern CCS, which appears to be driven by decreased upwelling favorable winds and enhanced stratification, and, for the HadGEM2-ES forced run, decreased nitrate content in upwelling source waters in nearshore regions. While trends in the downscaled models reflect those in the ESMs that force them, the ESM and downscaled solutions differ more for biogeochemical than for physical variables.

The Quilt of Sustainable Ocean Governance: Patterns for Practitioners - Robert L. Stephenson; Alistair J. Hobday; Edward H. Allison; Derek Armitage; Kate Brooks; Alida Bundy; Christopher Cvitanovic; Mark Dickey-Collas; Natalia de Miranda Grilli; Catalina Gomez; Astrid Jarre; Laura Kaikkonen; et al. (Frontiers in Marine Science, 2021)
In recent decades, scientists and practitioners have increasingly focused on identifying and codifying the best ways to manage activities in marine systems, leading to the development and implementation of concepts such as the social-ecological systems approach, ecosystem-based management, integrated management, marine spatial planning, participatory co-management, and the precautionary approach. To date, these concepts appear as separate entities: they have parallel literature streams; have been applied most often individually in attempts to improve governance and management; and in many ways, seem to be competing for attention. This patchwork of approaches may be hindering effective ocean governance. We propose that desirable features from these frameworks could be woven together to form the basis of more effective and equitable ocean governance arrangements across contexts, sectors, and scales. This article synthesizes the efforts of an IMBeR (Integrated Marine Biosphere Research Project) conference session and working group, that brought together experts in these diverse concepts with the objective of producing a synthesis of how they could be more effectively integrated for improved ocean sustainability outcomes. We reviewed and compared the concepts in terms of (a) the need to achieve a comprehensive suite of sustainability objectives, (b) similarities and differences in their scope, and (c) their place in practical management, policy and regulation. Achieving greater cross-sectoral integration, or a more holistic perspective on management for sustainability is at the core of each concept. All deal with aspects of governance and most, with improved participation in governance. The major differences in the origin and historical application of each concept are reflected in the degree of implicit or explicit focus given to different objectives of sustainability. Overall, the concepts are especially strong for ecological and institutional or governance considerations, moderately strong for economic aspects, and weakest for the social-cultural pillar of full spectrum sustainability. There is no panacea, and no emergent hierarchy among concepts. Some concepts fit better with top-down legislation-based efforts, others with more bottom-up stakeholder driven efforts. The selection of the core concepts for a situation will depend in a large part on which concepts are specified, or demand focus, in the legal and policy context of the situation (or area) of interest. No matter how influential or dominant a single concept might be, pragmatically, different concepts will be used in different areas, and there may always be the need for a combination of concepts and objectives woven together to achieve a cohesive quilt of sustainability.

Lower soil moisture and deep soil temperatures in thermokarst features increase old soil carbon loss after 10 years of experimental permafrost warming - Elaine F. Pegoraro; Marguerite E. Mauritz; Kiona Ogle; Christopher H. Ebert; Edward A. G. Schuur (Global Change Biology, 2021)
Almost half of the global terrestrial soil carbon (C) is stored in the northern circumpolar permafrost region, where air temperatures are increasing two times faster than the global average. As climate warms, permafrost thaws and soil organic matter becomes vulnerable to greater microbial decomposition. Long‐term soil warming of ice‐rich permafrost can result in thermokarst formation that creates variability in environmental conditions. Consequently, plant and microbial proportional contributions to ecosystem respiration may change in response to long‐term soil warming. Natural abundance δ 13 C and Δ 14 C of aboveground and belowground plant material, and of young and old soil respiration were used to inform a mixing model to partition the contribution of each source to ecosystem respiration fluxes. We employed a hierarchical Bayesian approach that incorporated gross primary productivity and environmental drivers to constrain source contributions. We found that long‐term experimental permafrost warming introduced a soil hydrology component that interacted with temperature to affect old soil C respiration. Old soil C loss was suppressed in plots with warmer deep soil temperatures because they tended to be wetter. When soil volumetric water content significantly decreased in 2018 relative to 2016 and 2017, the dominant respiration sources shifted from plant aboveground and young soil respiration to old soil respiration. The proportion of ecosystem respiration from old soil C accounted for up to 39% of ecosystem respiration and represented a 30‐fold increase compared to the wet‐year average. Our findings show that thermokarst formation may act to moderate microbial decomposition of old soil C when soil is highly saturated. However, when soil moisture decreases, a higher proportion of old soil C is vulnerable to decomposition and can become a large flux to the atmosphere. As permafrost systems continue to change with climate, we must understand the thresholds that may propel these systems from a C sink to a source.

Are physiological and behavioural responses to stressors displayed concordantly by wild urban rodents? - Loren L. Fardell; Miguel A. Bedoya-Pérez; Christopher R. Dickman; Mathew S. Crowther; Chris R. Pavey; Edward J. Narayan (The Science of Nature, 2021)
Understanding wild animal responses to stressors underpins effective wildlife management. In order for responses to stressors to be correctly interpreted, it is critical that measurements are taken on wild animals using minimally invasive techniques. Studies investigating wild animal responses to stressors often measure either a single physiological or behavioural variable, but whether such responses are comparable and concordant remains uncertain. We investigated this question in a pilot study that measured responses of wild-caught urban brown and black rats ( Rattus norvegicus , Rattus rattus ) to fur-based olfactory cues from a predator, the domestic cat ( Felis catus ); a novel herbivore, the koala ( Phascolarctos cinereus ); and a familiar herbivore and competitor, the common brushtail possum ( Trichosurus vulpecula ). Physiological responses, measured by assaying faecal glucocorticoid metabolites, were compared to behavioural responses observed via video recordings. We found that physiological and behavioural responses to stressors were expressed concordantly. There was no sizeable physiological response observed, and the behavioural response when considered across the night was negligible. However, the behavioural response to the predator and competitor cues changed across the observation period, with activity increasing with increasing hours of exposure. Our results indicate that responses of wild rodents to cues are nuanced, with stress responses modulated by behaviour changes that vary over time according to the severity of the perceived threat as animals gather further information. If the physiological response alone had been assessed, this moderated response may not have been evident, and in terms of wildlife management, vital information would have been lost.

Adverse Effects of Radiotherapy and Chemotherapy for Common Malignancies: What Is the Quality of Information Patients Are Finding Online? - Edward Christopher Dee; Grace Lee (Journal of Cancer Education, 2021)

Making sense of virus size and the tradeoffs shaping viral fitness - Kyle F. Edwards; Grieg F. Steward; Christopher R. Schvarcz (Ecology Letters, 2021)
Viruses span an impressive size range, with genome length varying a thousandfold and virion volume nearly a millionfold. For cellular organisms the scaling of traits with size is a pervasive influence on ecological processes, but whether size plays a central role in viral ecology is unknown. Here, we focus on viruses of aquatic unicellular organisms, which exhibit the greatest known range of virus size. We outline hypotheses within a quantitative framework, and analyse data where available, to consider how size affects the primary components of viral fitness. We argue that larger viruses have fewer offspring per infection and slower contact rates with host cells, but a larger genome tends to increase infection efficiency, broaden host range, and potentially increase attachment success and decrease decay rate. These countervailing selective pressures may explain why a breadth of sizes exist and even coexist when infecting the same host populations. Oligotrophic ecosystems may be enriched in “giant” viruses, because environments with resource‐limited phagotrophs at low concentrations may select for broader host range, better control of host metabolism, lower decay rate and a physical size that mimics bacterial prey. Finally, we describe where further research is needed to understand the ecology and evolution of viral size diversity.

Scenarios for Global Aquaculture and Its Role in Human Nutrition - Jessica A. Gephart; Christopher D. Golden; Frank Asche; Ben Belton; Cecile Brugere; Halley E. Froehlich; Jillian P. Fry; Benjamin S. Halpern; Christina C. Hicks; Robert C. Jones; Dane H. Klinger; David C. Little; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Plasticity in the grazing ecophysiology of Florenciella (Dichtyochophyceae), a mixotrophic nanoflagellate that consumes Prochlorococcus and other bacteria - Qian Li; Kyle F. Edwards; Christopher R. Schvarcz; Karen E. Selph; Grieg F. Steward (Limnology and Oceanography, 2021)
Mixotrophic nanoflagellates can account for more than half of the bacterivory in the sunlit ocean, yet very little is known about their ecophysiology. Here, we characterize the grazing ecology of an open‐ocean mixotroph in the genus Florenciella (class Dictyochophyceae). Members of this class were indirectly implicated as major consumers of Prochlorococcus and Synechococcus in the oligotrophic North Pacific Subtropical Gyre, but their phagotrophic capabilities have never been investigated. Our studies showed that Florenciella readily consumed Prochlorococcus , Synechococcus , and heterotrophic bacteria, and that the ingested prey relieved nutrient limitations on growth. Florenciella grew faster (3 d −1 ) in nitrogen‐deplete medium given sufficient live Synechococcus , than in nitrogen‐replete K medium (2 d −1 ), but it did not grow in continuous darkness. Grazing rates were substantially higher under nutrient limitation and showed a hint of diel variability, with rates tending to be highest near the end of the light period. An apparent trade‐off between the maximum clearance rate (5 nL Florenciella −1 h −1 ) and the maximum ingestion rate (up to ∼ 10 prey cells Florenciella −1 h −1 ) across experiments suggests that grazing behavior may also vary in response to prey concentration. If the observed grazing rates are representative of other open‐ocean mixotrophs, their collective activity could account for a significant fraction of the daily cyanobacterial mortality. This study provides essential parameters for understanding the grazing ecology of a common marine mixotroph and the first characterization of mixotrophic nanoflagellate functional responses when feeding on unicellular cyanobacteria, the dominant marine primary producers in the oligotrophic ocean.

Radiation Oncology Online: Quality, Strategies, and Disparities - Edward Christopher Dee; Nathan H. Varady (Journal of Cancer Education, 2020)

A review of American lobster (Homarus americanus) records around the British Isles: 2012 to 2018 - Christopher John Barrett; Alastair Cook; David Stone; Chris Evans; Debbie Murphy; Paul Johnson; Marc Thain; Gabrielle Wyn; Mark Grey; Hugh Edwards; Declan Quigley; Paul Douglas Stebbing (Hydrobiologia, 2020)

Bivalve Feeding Responses to Microalgal Bloom Species in the Indian River Lagoon: the Potential for Top-Down Control - Eve Galimany; Jessica Lunt; Christopher J. Freeman; Jay Houk; Thomas Sauvage; Larissa Santos; Jillian Lunt; Maria Kolmakova; Malcolm Mossop; Arthur Domingos; Edward J. Phlips; Valerie J. Paul (Estuaries and Coasts, 2020)
In 2011, the Indian River Lagoon, a biodiverse estuary in eastern Florida (USA), experienced an intense microalgal bloom with disastrous ecological consequences. The bloom included a mix of microalgae with unresolved taxonomy and lasted for 7 months with a maximum concentration of 130 μg chlorophyll a L −1 . In 2012, brown tide Aureoumbra lagunensis also bloomed in portions of this estuary, with reoccurrences in 2016 and 2018. To identify and understand the role of grazer pressure (top-down control) on bloom formation, we coupled DNA sequencing with bivalve feeding assays using three microalgae isolated from the 2011 bloom and maintained in culture. Feeding experiments were conducted on widely distributed bivalve species in the lagoon, including eastern oysters ( Crassostrea virginica ), hooked mussels ( Ischadium recurvum ), charru mussels ( Mytella charruana ), green mussels ( Perna viridis ), Atlantic rangia ( Rangia cuneata ), and hard clams ( Mercenaria mercenaria ), which were exposed to 3 × 10 4 cells mL −1 of five species of microalgae consisting of A. lagunensis and the three species clarified herein, the picocyanobacteria Crocosphaera sp. and ‘ Synechococcus ’ sp., and the picochlorophyte Picochlorum sp., as well as Nannochloropsis oculata used as a control. To ensure clearance rates were indicative of consumption and assimilation, the microalgae were isotopically ( 15 N) labeled prior to feeding experiments. Clearance rates differed among bivalve and microalgal species, but enriched 15 N values in bivalve tissue suggest that algal bloom species were assimilated by the bivalves. These results expand our understanding of the important ecosystem services that healthy, biodiverse filter feeder communities provide.

The unleashing of the immune system in COVID-19 and sepsis: the calm before the storm? - Salvatore Bellinvia; Christopher J. Edwards; Matteo Schisano; Paolo Banfi; Matteo Fallico; Paolo Murabito (Inflammation Research, 2020)

Red-tailed monkeys (Cercopithecus ascanius) prey upon and mob birds in the Issa Valley, western Tanzania - Christopher W. Lile; Edward McLester; Fiona A. Stewart; Alex K. Piel (Primates, 2020)

Not Thinking of Applause - Edward Christopher Dee (Journal of Cancer Education, 2020)

Vagococcus salmoninarum I—A chronic coldwater streptococcosis in broodstock brook trout ( Salvelinus fontinalis ) in Wisconsin, USA - Isaac Standish; Sara Erickson; Eric Leis; Wes Baumgartner; Thomas Loch; Christopher Knupp; Rebekah McCann; Corey Puzach; Ryan Katona; Ellen Lark; Jennifer Bailey; Jorge Buening; et al. (Journal of Fish Diseases, 2020)
In 2018, Vagococcus salmoninarum was isolated from two lots of broodstock “coaster” brook trout ( Salvelinus fontinalis ) containing ~1,500 fish at the Iron River National Fish Hatchery, at which time it was identified as the causative agent of a chronic coldwater streptococcosis epizootic. Clinical signs included exophthalmia, lethargy, erratic swimming and loss of equilibrium. Female fish experienced disproportionately higher morbidity and mortality than male co‐inhabitants, and routinely retained eggs following spawning. The most consistent gross clinical sign was heart pallor and turbid pericardial effusion. An attempted treatment using florfenicol was ineffective at halting the epizootic, which spanned more than a year and resulted in >50% mortality before remaining fish were culled. As there is no previous documentation of V. salmoninarum at this hatchery or in this species, it is still unclear what circumstances led to this epizootic. The inability to treat this chronic disease led to the loss of valuable broodstock, hampering ongoing fishery conservation efforts in the Great Lakes Basin.

Complete genome sequence of bovine herpesvirus type 1.1 (BoHV-1.1) Los Angeles (LA) strain and its genotypic relationship to BoHV-1.1 Cooper and more recently isolated wild-type field strains - Jean M. d’Offay; Robert W. Fulton; R. Eberle; Edward J. Dubovi; Christopher C. L. Chase (Archives of Virology, 2019)

Observational Needs of Sea Surface Temperature - Anne G. O’Carroll; Edward M. Armstrong; Helen M. Beggs; Marouan Bouali; Kenneth S. Casey; Gary K. Corlett; Prasanjit Dash; Craig J. Donlon; Chelle L. Gentemann; Jacob L. Høyer; Alexander Ignatov; Kamila Kabobah; et al. (Frontiers in Marine Science, 2019)

Modeling Environmental DNA Transport in the Coastal Ocean Using Lagrangian Particle Tracking - Elizabeth A. Andruszkiewicz; Jeffrey R. Koseff; Oliver B. Fringer; Nicholas T. Ouellette; Anna B. Lowe; Christopher A. Edwards; Alexandria B. Boehm (Frontiers in Marine Science, 2019)

Model-Observations Synergy in the Coastal Ocean - Pierre De Mey-Frémaux; Nadia Ayoub; Alexander Barth; Robert Brewin; Guillaume Charria; Francisco Campuzano; Stefano Ciavatta; Mauro Cirano; Christopher A. Edwards; Ivan Federico; Shan Gao; Isabel Garcia Hermosa; et al. (Frontiers in Marine Science, 2019)

Surface and subsurface N2O losses from dairy cropping systems - Jessica Quesnel; Andrew C. VanderZaag; Anna Crolla; Christopher Kinsley; Edward G. Gregorich; Claudia Wagner-Riddle (Nutrient Cycling in Agroecosystems, 2019)

Ten tips for developing interdisciplinary socio-ecological researchers - Rachel Kelly; Mary Mackay; Kirsty L. Nash; Christopher Cvitanovic; Edward H. Allison; Derek Armitage; Aletta Bonn; Steven J. Cooke; Stewart Frusher; Elizabeth A. Fulton; Benjamin S. Halpern; Priscila F. M. Lopes; et al. (Socio-Ecological Practice Research, 2019)

Intestinal nerve cell injury occurs prior to insulin resistance in female mice ingesting a high-fat diet - Yvonne Nyavor; Rachel Estill; Hannah Edwards; Hailey Ogden; Kaila Heideman; Kiefer Starks; Christopher Miller; George May; Lance Flesch; John McMillan; Martin Gericke; Larry Forney; et al. (Cell and Tissue Research, 2019)

Better Regional Ocean Observing Through Cross-National Cooperation: A Case Study From the Northeast Pacific - John A. Barth; Susan E. Allen; Edward P. Dever; Richard K. Dewey; Wiley Evans; Richard A. Feely; Jennifer L. Fisher; Jonathan P. Fram; Burke Hales; Debby Ianson; Jennifer Jackson; Kim Juniper; et al. (Frontiers in Marine Science, 2019)

Advancing Marine Biogeochemical and Ecosystem Reanalyses and Forecasts as Tools for Monitoring and Managing Ecosystem Health - Katja Fennel; Marion Gehlen; Pierre Brasseur; Christopher W. Brown; Stefano Ciavatta; Gianpiero Cossarini; Alessandro Crise; Christopher A. Edwards; David Ford; Marjorie A. M. Friedrichs; Marilaure Gregoire; Emlyn Jones; et al. (Frontiers in Marine Science, 2019)

Mitochondrial health and muscle plasticity after spinal cord injury - Ashraf S. Gorgey; Oksana Witt; Laura O’Brien; Christopher Cardozo; Qun Chen; Edward J. Lesnefsky; Zachary A. Graham (European Journal of Applied Physiology, 2019)

Development of community of practice to support quantitative risk assessment for synthetic biology products: contaminant bioremediation and invasive carp control as cases - Benjamin D. Trump; Christy Foran; Taylor Rycroft; Matthew D. Wood; Nirzwan Bandolin; Mariana Cains; Timothy Cary; Fiona Crocker; Nicholas A. Friedenberg; Patrick Gurian; Kerry Hamilton; Jan Jeffrey Hoover; et al. (Environment Systems and Decisions, 2018)

Evolutionarily stable communities: a framework for understanding the role of trait evolution in the maintenance of diversity - Kyle F. Edwards; Colin T. Kremer; Elizabeth T. Miller; Matthew M. Osmond; Elena Litchman; Christopher A. Klausmeier (Ecology Letters, 2018)
Biological diversity depends on the interplay between evolutionary diversification and ecological mechanisms allowing species to coexist. Current research increasingly integrates ecology and evolution over a range of timescales, but our common conceptual framework for understanding species coexistence requires better incorporation of evolutionary processes. Here, we focus on the idea of evolutionarily stable communities ( ESC s), which are theoretical endpoints of evolution in a community context. We use ESC s as a unifying framework to highlight some important but under‐appreciated theoretical results, and we review empirical research relevant to these theoretical predictions. We explain how, in addition to generating diversity, evolution can also limit diversity by reducing the effectiveness of coexistence mechanisms. The coevolving traits of competing species may either diverge or converge, depending on whether the number of species in the community is low (undersaturated) or high (oversaturated) relative to the ESC . Competition in oversaturated communities can lead to extinction or neutrally coexisting, ecologically equivalent species. It is critical to consider trait evolution when investigating fundamental ecological questions like the strength of different coexistence mechanisms, the feasibility of ecologically equivalent species, and the interpretation of different patterns of trait dispersion.

Biotic responses buffer warming‐induced soil organic carbon loss in Arctic tundra - Junyi Liang; Jiangyang Xia; Zheng Shi; Lifen Jiang; Shuang Ma; Xingjie Lu; Marguerite Mauritz; Susan M. Natali; Elaine Pegoraro; Christopher Ryan Penton; César Plaza; Verity G. Salmon; et al. (Global Change Biology, 2018)
Climate warming can result in both abiotic (e.g., permafrost thaw) and biotic (e.g., microbial functional genes) changes in Arctic tundra. Recent research has incorporated dynamic permafrost thaw in Earth system models ( ESM s) and indicates that Arctic tundra could be a significant future carbon (C) source due to the enhanced decomposition of thawed deep soil C. However, warming‐induced biotic changes may influence biologically related parameters and the consequent projections in ESM s. How model parameters associated with biotic responses will change under warming and to what extent these changes affect projected C budgets have not been carefully examined. In this study, we synthesized six data sets over 5 years from a soil warming experiment at the Eight Mile Lake, Alaska, into the Terrestrial ECO system ( TECO ) model with a probabilistic inversion approach. The TECO model used multiple soil layers to track dynamics of thawed soil under different treatments. Our results show that warming increased light use efficiency of vegetation photosynthesis but decreased baseline (i.e., environment‐corrected) turnover rates of SOC in both the fast and slow pools in comparison with those under control. Moreover, the parameter changes generally amplified over time, suggesting processes of gradual physiological acclimation and functional gene shifts of both plants and microbes. The TECO model predicted that field warming from 2009 to 2013 resulted in cumulative C losses of 224 or 87 g/m 2 , respectively, without or with changes in those parameters. Thus, warming‐induced parameter changes reduced predicted soil C loss by 61%. Our study suggests that it is critical to incorporate biotic changes in ESM s to improve the model performance in predicting C dynamics in permafrost regions.

Motile Dendritic Cells Sense and Respond to Substrate Geometry - Amy C. Bendell; Nicholas Anderson; Daniel Blumenthal; Edward K. Williamson; Christopher S. Chen; Janis K. Burkhardt; Daniel A. Hammer (Annals of Biomedical Engineering, 2018)

Critical comparison of molecular methods for detection and enumeration of the harmful algal species, Heterosigma akashiwo, in environmental water samples - Christopher R. Main; Dianne I. Greenfield; Cameron Doll; Yanfei Wang; Edward B. Whereat; Rebecca Mortensen; D. Tye Pettay; Kathryn J. Coyne (Journal of Applied Phycology, 2018)

Spatiotemporal heterogeneity and patterning of developing renal blood vessels - Edward Daniel; D. Berfin Azizoglu; Anne R. Ryan; Tezin A. Walji; Christopher P. Chaney; Gabrielle I. Sutton; Thomas J. Carroll; Denise K. Marciano; Ondine Cleaver (Angiogenesis, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Integrating Dynamic Subsurface Habitat Metrics Into Species Distribution Models - Stephanie Brodie; Michael G. Jacox; Steven J. Bograd; Heather Welch; Heidi Dewar; Kylie L. Scales; Sara M. Maxwell; Dana M. Briscoe; Christopher A. Edwards; Larry B. Crowder; Rebecca L. Lewison; Elliott L. Hazen (Frontiers in Marine Science, 2018)

Comparative, collaborative, and integrative risk governance for emerging technologies - Igor Linkov; Benjamin D. Trump; Elke Anklam; David Berube; Patrick Boisseasu; Christopher Cummings; Scott Ferson; Marie-Valentine Florin; Bernard Goldstein; Danail Hristozov; Keld Alstrup Jensen; Georgios Katalagarianakis; et al. (Environment Systems and Decisions, 2018)

Interactions among plants, bacteria, and fungi reduce extracellular enzyme activities under long‐term N fertilization - Joseph E. Carrara; Christopher A. Walter; Jennifer S. Hawkins; William T. Peterjohn; Colin Averill; Edward R. Brzostek (Global Change Biology, 2018)
Atmospheric nitrogen (N) deposition has enhanced soil carbon (C) stocks in temperate forests. Most research has posited that these soil C gains are driven primarily by shifts in fungal community composition with elevated N leading to declines in lignin degrading Basidiomycetes . Recent research, however, suggests that plants and soil microbes are dynamically intertwined, whereby plants send C subsidies to rhizosphere microbes to enhance enzyme production and the mobilization of N. Thus, under elevated N, trees may reduce belowground C allocation leading to cascading impacts on the ability of microbes to degrade soil organic matter through a shift in microbial species and/or a change in plant–microbe interactions. The objective of this study was to determine the extent to which couplings among plant, fungal, and bacterial responses to N fertilization alter the activity of enzymes that are the primary agents of soil decomposition. We measured fungal and bacterial community composition, root–microbial interactions, and extracellular enzyme activity in the rhizosphere, bulk, and organic horizon of soils sampled from a long‐term (>25 years), whole‐watershed, N fertilization experiment at the Fernow Experimental Forest in West Virginia, USA. We observed significant declines in plant C investment to fine root biomass (24.7%), root morphology, and arbuscular mycorrhizal (AM) colonization (55.9%). Moreover, we found that declines in extracellular enzyme activity were significantly correlated with a shift in bacterial community composition, but not fungal community composition. This bacterial community shift was also correlated with reduced AM fungal colonization indicating that declines in plant investment belowground drive the response of bacterial community structure and function to N fertilization. Collectively, we find that enzyme activity responses to N fertilization are not solely driven by fungi, but instead reflect a whole ecosystem response, whereby declines in the strength of belowground C investment to gain N cascade through the soil environment.

Air–Sea/Land Interaction in the Coastal Zone - Andrey A. Grachev; Laura S. Leo; Harindra J. S. Fernando; Christopher W. Fairall; Edward Creegan; Byron W. Blomquist; Adam J. Christman; Christopher M. Hocut (Boundary-Layer Meteorology, 2018)

Unrecognized species diversity and new insights into colour pattern polymorphism within the widespread Malagasy snake Mimophis (Serpentes: Lamprophiidae) - Sara Ruane; Edward A. Myers; Kahmun Lo; Sara Yuen; Rachel S. Welt; Maya Juman; India Futterman; Ronald A. Nussbaum; Gregory Schneider; Frank T. Burbrink; Christopher J. Raxworthy (Systematics and Biodiversity, 2018)

An evaluation of Z-transform algorithms for identifying subject-specific abnormalities in neuroimaging data - Andrew R. Mayer; Andrew B. Dodd; Josef M. Ling; Christopher J. Wertz; Nicholas A. Shaff; Edward J. Bedrick; Carlo Viamonte (Brain Imaging and Behavior, 2018)

TOX3 Variants Are Involved in Restless Legs Syndrome and Parkinson’s Disease with Opposite Effects - Sadaf Mohtashami; Qin He; Jennifer A. Ruskey; Sirui Zhou; Patrick A. Dion; Richard P. Allen; Christopher J. Earley; Edward A. Fon; Lan Xiong; Nicolas Dupre; Yves Dauvilliers; Guy A. Rouleau; et al. (Journal of Molecular Neuroscience, 2018)

Microbial functional diversity covaries with permafrost thaw‐induced environmental heterogeneity in tundra soil - Mengting M. Yuan; Jin Zhang; Kai Xue; Liyou Wu; Ye Deng; Jie Deng; Lauren Hale; Xishu Zhou; Zhili He; Yunfeng Yang; Joy D. Van Nostrand; Edward A. G. Schuur; et al. (Global Change Biology, 2018)
Permafrost soil in high latitude tundra is one of the largest terrestrial carbon (C) stocks and is highly sensitive to climate warming. Understanding microbial responses to warming‐induced environmental changes is critical to evaluating their influences on soil biogeochemical cycles. In this study, a functional gene array (i.e., geochip 4.2) was used to analyze the functional capacities of soil microbial communities collected from a naturally degrading permafrost region in Central Alaska. Varied thaw history was reported to be the main driver of soil and plant differences across a gradient of minimally, moderately, and extensively thawed sites. Compared with the minimally thawed site, the number of detected functional gene probes across the 15–65 cm depth profile at the moderately and extensively thawed sites decreased by 25% and 5%, while the community functional gene β‐diversity increased by 34% and 45%, respectively, revealing decreased functional gene richness but increased community heterogeneity along the thaw progression. Particularly, the moderately thawed site contained microbial communities with the highest abundances of many genes involved in prokaryotic C degradation, ammonification, and nitrification processes, but lower abundances of fungal C decomposition and anaerobic‐related genes. Significant correlations were observed between functional gene abundance and vascular plant primary productivity, suggesting that plant growth and species composition could be co‐evolving traits together with microbial community composition. Altogether, this study reveals the complex responses of microbial functional potentials to thaw‐related soil and plant changes and provides information on potential microbially mediated biogeochemical cycles in tundra ecosystems.

Functional connectivity abnormalities and associated cognitive deficits in fetal alcohol Spectrum disorders (FASD) - Jeffrey R. Wozniak; Bryon A. Mueller; Sarah N. Mattson; Claire D. Coles; Julie A. Kable; Kenneth L. Jones; Christopher J. Boys; Kelvin O. Lim; Edward P. Riley; Elizabeth R. Sowell (Brain Imaging and Behavior, 2017)

Stable isotope analysis in deep-sea chondrichthyans: recent challenges, ecological insights, and future directions - Oliver. N. Shipley; Edward J. Brooks; Daniel J. Madigan; Christopher J. Sweeting; R. Dean Grubbs (Reviews in Fish Biology and Fisheries, 2017)

Effects of nalfurafine on the reinforcing, thermal antinociceptive, and respiratory-depressant effects of oxycodone: modeling an abuse-deterrent opioid analgesic in rats - E. Andrew Townsend; Jennifer E. Naylor; S. Stevens Negus; Shelley R. Edwards; Hina N. Qureshi; Hunter W. McLendon; Christopher R. McCurdy; Coco N. Kapanda; Jussara M. do Carmo; Fernanda S. da Silva; John E. Hall; Kenneth J. Sufka; et al. (Psychopharmacology, 2017)

Does Aquaculture Support the Needs of Nutritionally Vulnerable Nations? - Christopher D. Golden; Katherine L. Seto; Madan M. Dey; Oai L. Chen; Jessica A. Gephart; Samuel S. Myers; Matthew Smith; Bapu Vaitla; Edward H. Allison (Frontiers in Marine Science, 2017)

Markers of physiological stress during exercise under conditions of normoxia, normobaric hypoxia, hypobaric hypoxia, and genuine high altitude - David Richard Woods; John Paul O’Hara; Christopher John Boos; Peter David Hodkinson; Costas Tsakirides; Neil Edward Hill; Darren Jose; Amanda Hawkins; Kelly Phillipson; Antonia Hazlerigg; Nicola Arjomandkhah; Liam Gallagher; et al. (European Journal of Applied Physiology, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Specification of a Coupled Geological and Wellbore Fluid Dynamics Model for Uncertainty Analysis and Risk-Based Design on a Subsea Oil Project - Christopher J. Jablonowski; Arash Haghshenas; Edward E. Shumilak; Kenneth F. Tyler (Natural Resources Research, 2017)

Suspected Adulteration of Commercial Kratom Products with 7-Hydroxymitragynine - Alicia G. Lydecker; Abhisheak Sharma; Christopher R. McCurdy; Bonnie A. Avery; Kavita M. Babu; Edward W. Boyer (Journal of Medical Toxicology, 2016)

Chest wall motion analysis in healthy volunteers and adults with cystic fibrosis using a novel Kinect-based motion tracking system - James M. Harte; Christopher K. Golby; Johanna Acosta; Edward F. Nash; Ercihan Kiraci; Mark A. Williams; Theodoros N. Arvanitis; Babu Naidu (Medical & Biological Engineering & Computing, 2016)

Weathering of Oil Spilled in the Marine Environment - Matthew Tarr; Pheobe Zito; Edward Overton; Gregory Olson; Puspa Adkikari; Christopher Reddy (Oceanography, 2016)

Mapping adipose and muscle tissue expression quantitative trait loci in African Americans to identify genes for type 2 diabetes and obesity - Satria P. Sajuthi; Neeraj K. Sharma; Jeff W. Chou; Nicholette D. Palmer; David R. McWilliams; John Beal; Mary E. Comeau; Lijun Ma; Jorge Calles-Escandon; Jamehl Demons; Samantha Rogers; Kristina Cherry; et al. (Human Genetics, 2016)

Variability in the response of amphipods and macroinvertebrate assemblage structure to prolonged drought in forested upland streams - Samantha J. Imberger; Christopher J. Walsh; Edward Tsyrlin; David G. Kerr; Monica Tewman (Biodiversity and Conservation, 2016)

Phytoplankton growth and the interaction of light and temperature: A synthesis at the species and community level - Kyle F. Edwards; Mridul K. Thomas; Christopher A. Klausmeier; Elena Litchman (Limnology and Oceanography, 2016)
Temperature strongly affects phytoplankton growth rates, but its effect on communities and ecosystem processes is debated. Because phytoplankton are often limited by light, temperature should change community structure if it affects the traits that determine competition for light. Furthermore, the aggregate response of phytoplankton communities to temperature will depend on how changes in community structure scale up to bulk rates. Here, we synthesize experiments on 57 phytoplankton species to analyze how the growth‐irradiance relationship changes with temperature. We find that light‐limited growth, light‐saturated growth, and the optimal irradiance for growth are all highly sensitive to temperature. Within a species, these traits are co‐adapted to similar temperature optima, but light‐limitation reduces a species' temperature optimum by ∼5°C, which may be an adaptation to how light and temperature covary with depth or reflect underlying physiological correlations. Importantly, the maximum achievable growth rate increases with temperature under light saturation, but not under strong light limitation. This implies that light limitation diminishes the temperature sensitivity of bulk phytoplankton growth, even though community structure will be temperature‐sensitive. Using a database of primary production incubations, we show that this prediction is consistent with estimates of bulk phytoplankton growth across gradients of temperature and irradiance in the ocean. These results indicate that interactions between temperature and resource limitation will be fundamental for explaining how phytoplankton communities and biogeochemical processes vary across temperature gradients and respond to global change.

Evaluation of cystatin C as an early biomarker of cadmium nephrotoxicity in the rat - Walter C. Prozialeck; Aaron VanDreel; Christopher D. Ackerman; Ian Stock; Alexander Papaeliou; Christian Yasmine; Kristen Wilson; Peter C. Lamar; Victoria L. Sears; Joshua Z. Gasiorowski; Karyn M. DiNovo; Vishal S. Vaidya; et al. (BioMetals, 2016)

Initial evaluations of a Gulf of Mexico/Caribbean ocean forecast system in the context of the Deepwater Horizon disaster - Edward D. Zaron; Patrick J. Fitzpatrick; Scott L. Cross; John M. Harding; Frank L. Bub; Jerry D. Wiggert; Dong S. Ko; Yee Lau; Katharine Woodard; Christopher N. K. Mooers (Frontiers of Earth Science, 2015)

Seascape drivers of M acrocystis pyrifera population genetic structure in the northeast P acific - Mattias L. Johansson; Filipe Alberto; Daniel C. Reed; Peter T. Raimondi; Nelson C. Coelho; Mary A. Young; Patrick T. Drake; Christopher A. Edwards; Kyle Cavanaugh; Jorge Assis; Lydia B. Ladah; Tom W. Bell; et al. (Molecular Ecology, 2015)
At small spatial and temporal scales, genetic differentiation is largely controlled by constraints on gene flow, while genetic diversity across a species' distribution is shaped on longer temporal and spatial scales. We assess the hypothesis that oceanographic transport and other seascape features explain different scales of genetic structure of giant kelp, M acrocystis pyrifera . We followed a hierarchical approach to perform a microsatellite‐based analysis of genetic differentiation in M acrocystis across its distribution in the northeast P acific. We used seascape genetic approaches to identify large‐scale biogeographic population clusters and investigate whether they could be explained by oceanographic transport and other environmental drivers. We then modelled population genetic differentiation within clusters as a function of oceanographic transport and other environmental factors. Five geographic clusters were identified: A laska/ C anada, central C alifornia, continental S anta B arbara, C alifornia C hannel I slands and mainland southern C alifornia/ B aja C alifornia peninsula. The strongest break occurred between central and southern C alifornia, with mainland S anta B arbara sites forming a transition zone between the two. Breaks between clusters corresponded approximately to previously identified biogeographic breaks, but were not solely explained by oceanographic transport. An isolation‐by‐environment ( IBE ) pattern was observed where the northern and southern C hannel I slands clustered together, but not with closer mainland sites, despite the greater distance between them. The strongest environmental association with this IBE pattern was observed with light extinction coefficient, which extends suitable habitat to deeper areas. Within clusters, we found support for previous results showing that oceanographic connectivity plays an important role in the population genetic structure of M acrocystis in the Northern hemisphere.

Toward the genetic origins of a potentially non-native population of threespine stickleback (Gasterosteus aculeatus) in Alberta - Andrew M. Rezansoff; Erika Crispo; Christopher Blair; Edward Cruz; Jun Kitano; Steven M. Vamosi; Sean M. Rogers (Conservation Genetics, 2015)

Nutrient utilization traits of phytoplankton - Kyle F. Edwards; Christopher A. Klausmeier; Elena Litchman (Ecology, 2015)
This paper presents a compilation of nutrient utilization traits of marine and freshwater phytoplankton. The literature was comprehensively searched for culture experiments using nitrate, ammonium, or phosphate as the limiting nutrient. The following traits were extracted: the response of growth to nutrient supply (maximum growth rate under unlimited nutrient supply and the nutrient concentration at which growth is half‐saturated); the response of internal nutrient content to nutrient supply (the minimum subsistence quota at which growth ceases and the maximum nutrient quota under unlimited nutrient supply); and nutrient uptake kinetics for nutrient‐limited cells (maximum uptake rate and the nutrient concentration at which uptake is half‐saturated). The resulting data set includes 1319 measurements on 129 species from 138 publications. Potential uses of these data include studies of community structure and trait evolution, parameterization of ecosystem models, and biofuel development.

Tolerance of wheat to vegetative stage soil waterlogging is conditioned by both constitutive and adaptive QTL - Diana C. Ballesteros; R. Esten Mason; Christopher K. Addison; M. Andrea Acuña; M. Nelly Arguello; Nithya Subramanian; Randall Galen Miller; Haley Sater; Edward E. Gbur; David Miller; Carl A. Griffey; Marla D. Barnett; et al. (Euphytica, 2015)

Expression of the Mannose Receptor CD206 in HIV and SIV Encephalitis: A Phenotypic Switch of Brain Perivascular Macrophages with Virus Infection - Gerard E. Holder; Christopher M. McGary; Edward M. Johnson; Rubo Zheng; Vijay T. John; Chie Sugimoto; Marcelo J. Kuroda; Woong-Ki Kim (Journal of Neuroimmune Pharmacology, 2014)

ERAP1 in the pathogenesis of ankylosing spondylitis - Emma Reeves; Tim Elliott; Edward James; Christopher J. Edwards (Immunologic Research, 2014)

A Multidisciplinary Conceptualization of Conservation Opportunity - KATIE MOON; VANESSA M. ADAMS; STEPHANIE R. JANUCHOWSKI‐HARTLEY; MAKSYM POLYAKOV; MORENA MILLS; DUAN BIGGS; ANDREW T. KNIGHT; EDWARD T. GAME; CHRISTOPHER M. RAYMOND (Conservation Biology, 2014)
An opportunity represents an advantageous combination of circumstances that allows goals to be achieved. We reviewed the nature of opportunity and how it manifests in different subsystems (e.g., biophysical, social, political, economic) as conceptualized in other bodies of literature, including behavior, adoption, entrepreneur, public policy, and resilience literature. We then developed a multidisciplinary conceptualization of conservation opportunity. We identified 3 types of conservation opportunity: potential , actors remove barriers to problem solving by identifying the capabilities within the system that can be manipulated to create support for conservation action; traction , actors identify windows of opportunity that arise from exogenous shocks, events, or changes that remove barriers to solving problems; and existing , everything is in place for conservation action (i.e., no barriers exist) and an actor takes advantage of the existing circumstances to solve problems. Different leverage points characterize each type of opportunity. Thus, unique stages of opportunity identification or creation and exploitation exist: characterizing the system and defining problems; identifying potential solutions; assessing the feasibility of solutions; identifying or creating opportunities; and taking advantage of opportunities. These stages can be undertaken independently or as part of a situational analysis and typically comprise the first stage, but they can also be conducted iteratively throughout a conservation planning process. Four types of entrepreneur can be identified (business, policy, social, and conservation), each possessing attributes that enable them to identify or create opportunities and take advantage of them. We examined how different types of conservation opportunity manifest in a social–ecological system (the Great Barrier Reef) and how they can be taken advantage of. Our multidisciplinary conceptualization of conservation opportunity strengthens and legitimizes the concept.

Non-linear Increases in Danazol Exposure with Dose in Older vs. Younger Beagle Dogs: The Potential Role of Differences in Bile Salt Concentration, Thermodynamic Activity, and Formulation Digestion - Mette U. Anby; Hywel D. Williams; Orlagh Feeney; Glenn A. Edwards; Hassan Benameur; Colin W. Pouton; Christopher J. H. Porter (Pharmaceutical Research, 2014)

Amphiphilic triblock copolymers with PEGylated hydrocarbon structures as environmentally friendly marine antifouling and fouling-release coatings - Zhaoli Zhou; David R. Calabrese; Warren Taylor; John A. Finlay; Maureen E. Callow; James A. Callow; Daniel Fischer; Edward J. Kramer; Christopher K. Ober (Biofouling, 2014)

Erratum to: A genome-wide association study of prostate cancer in West African men - Michael Blaise Cook; Zhaoming Wang; Edward D. Yeboah; Yao Tettey; Richard B. Biritwum; Andrew A. Adjei; Evelyn Tay; Ann Truelove; Shelley Niwa; Charles C. Chung; Annand P. Chokkalingam; Lisa W. Chu; et al. (Human Genetics, 2014)

A genome-wide association study of prostate cancer in West African men - Michael Blaise Cook; Zhaoming Wang; Edward D. Yeboah; Yao Tettey; Richard B. Biritwum; Andrew A. Adjei; Evelyn Tay; Ann Truelove; Shelley Niwa; Charles C. Chung; Annand P. Chokkalingam; Lisa W. Chu; et al. (Human Genetics, 2014)

Spontaneous onset of complex regional pain syndrome Type I in a woman infected with Bartonella koehlerae - Cristina Pérez Vera; Ricardo G. Maggi; Christopher W. Woods; Patricia E. Mascarelli; Edward B. Breitschwerdt (Medical Microbiology and Immunology, 2014)

Production Factors Controlling the Physical Characteristics of Biochar Derived from Phytoremediation Willow for Agricultural Applications - Ashleigh J. Fletcher; Malcolm A. Smith; Andreas Heinemeyer; Richard Lord; Christopher J. Ennis; Edward M. Hodgson; Kerrie Farrar (BioEnergy Research, 2014)

GEOTRACES: Changing the Way We Explore Ocean Chemistry - Robert Anderson; Edward Mawji; Gregory Cutter; Christopher Measures; Catherine Jeandel (Oceanography, 2014)

Atmospheric and oceanic climate forcing of the exceptional Greenland ice sheet surface melt in summer 2012 - Edward Hanna; Xavier Fettweis; Sebastian H. Mernild; John Cappelen; Mads H. Ribergaard; Christopher A. Shuman; Konrad Steffen; Len Wood; Thomas L. Mote (International Journal of Climatology, 2014)
The NASA announcement of record surface melting of the Greenland ice sheet in July 2012 led us to examine the atmospheric and oceanic climatic anomalies that are likely to have contributed to these exceptional conditions and also to ask the question of how unusual these anomalies were compared to available records. Our analysis allows us to assess the relative contributions of these two key influences to both the extreme melt event and ongoing climate change. In 2012, as in recent warm summers since 2007, a blocking high pressure feature, associated with negative NAO conditions, was present in the mid‐troposphere over Greenland for much of the summer. This circulation pattern advected relatively warm southerly winds over the western flank of the ice sheet, forming a ‘heat dome’ over Greenland that led to the widespread surface melting. Both sea‐surface temperature and sea‐ice cover anomalies seem to have played a minimal role in this record melt, relative to atmospheric circulation. Two representative coastal climatological station averages and several individual stations in south, west and north‐west Greenland set new surface air temperature records for May, June, July and the whole ( JJA ) summer. The unusually warm summer 2012 conditions extended to the top of the ice sheet at Summit, where our reanalysed (1994–2012) DMI Summit weather station summer ( JJA ) temperature series set new record high mean and extreme temperatures in 2012; 3‐hourly instantaneous 2‐m temperatures reached an exceptional value of 2.2°C at Summit on 11 July 2012. These conditions translated into the record observed ice‐sheet wide melt during summer 2012. However, 2012 seems not to be climatically representative of future ‘average’ summers projected this century.

Land surface skin temperature captures thermal environments of C 3 and C 4 grasses - Christopher J. Still; Stephanie Pau; Erika J. Edwards (Global Ecology and Biogeography, 2014)
Aim Numerous studies have documented ecological sorting of C 3 and C 4 grasses along air temperature gradients. However, phylogenetically structured analyses suggest that closely related C 3 and C 4 grasses (in the same PACMAD clade: P anicoideae, A rundinoideae, C hloridoideae, M icrairoideae, A ristidoideae and D anthonioideae) occur in environments with similar air temperature, challenging our understanding of how the photosynthetic pathway influences grass biogeography. To better understand thermal differences between C 3 and C 4 grass lineages, we analysed the surface radiative temperature as an alternative measure that is more closely aligned with plant microclimate. Location H awaiian I slands, USA . Methods We used the MODIS land surface temperature ( LST ) product, a satellite‐based measurement of radiative temperature. We compared LST with mean annual air temperature ( MAT ) for locations where C 3 and C 4 grass species were collected. We also utilized other satellite products, like MODIS tree cover, as a proxy for relative habitat openness where these grasses occur. Results Comparisons of C 3 lineages [in BEP ( B ambusoideae, E hrhartoideae and P ooideae) and PACMAD clades] and C 4 lineages ( PACMAD clade only) illustrate the differing thermal environments for each group. C 4 taxa are found in the environments with the highest MAT , followed by C 3 PACMAD species. By contrast, C 3 PACMAD species are found in the environments with the coolest LST , and the LST values for C 3 BEP species are substantially higher than their MAT values. The difference in LST between C 3 and C 4 PACMADs is larger than the difference in MAT between these groups. Main conclusions Though LST has been used infrequently in ecology and biogeography, it is intimately related to water and energy balance and ecosystem structure, and should more accurately capture plant temperatures and microclimates than MAT . Our results provide support for a pronounced thermal difference in the environments of closely related C 3 and C 4 grass taxa, and show that C 3 PACMADs occur in the coolest and least variable thermal environments, probably due to the greater tree cover of these habitats.

Improving the science-policy dialogue to meet the challenges of biodiversity conservation: having conversations rather than talking at one-another - Juliette C. Young; Kerry A. Waylen; Simo Sarkki; Steve Albon; Ian Bainbridge; Estelle Balian; James Davidson; David Edwards; Roddy Fairley; Ceri Margerison; Davy McCracken; Roger Owen; et al. (Biodiversity and Conservation, 2014)

Modeled diversity effects on microbial ecosystem functions of primary production, nutrient uptake, and remineralization - Nicole L. Goebel; Christopher A. Edwards; Michael J. Follows; Jonathan P. Zehr (Ecology, 2014)
Ecosystem‐wide primary productivity generally increases with primary producer diversity, emphasizing the importance of diversity for ecosystem function. However, most studies that demonstrate this positive relationship have focused on terrestrial and aquatic benthic systems, with little attention to the diverse marine pelagic primary producers that play an important role in regulating global climate. Here we show how phytoplankton biodiversity enhances overall marine ecosystem primary productivity and other ecosystem functions using a self‐organizing ecosystem model. Diversity manipulation numerical experiments reveal positive, asymptotically saturating relationships between ecosystem‐wide phytoplankton diversity and functions of productivity, nutrient uptake, remineralization, and diversity metrics used to identify mechanisms shaping these relationships. Increase in productivity with increasing diversity improves modeled ecosystem stability and model robustness and leads to productivity rates that exceed expected yields primarily through niche complementarity and facilitative interactions between coexisting phytoplankton types; the composition of traits in assemblages determines the magnitude of complementarity and selection effects. While findings based on these aggregate measures of diversity effects parallel those from the majority of experimental outcomes of terrestrial and benthic biodiversity–ecosystem function studies, we combine analyses of community diversity effects and investigations of the underlying interactions among phytoplankton types to demonstrate how an increase in recycled production of non‐diatoms through an increase in new production of diatoms drives this diversity–ecosystem function response. We demonstrate the important role that facilitation plays in the modeled marine plankton and how this facilitative interaction could amplify future climate‐driven changes in ocean ecosystem productivity.

The N-glycoform of sRAGE is the key determinant for its therapeutic efficacy to attenuate injury-elicited arterial inflammation and neointimal growth - Hyun-Jin Tae; Ji Min Kim; Sungha Park; Noboru Tomiya; Geng Li; Wen Wei; Natalia Petrashevskaya; Ismayil Ahmet; John Pang; Stefanie Cruschwitz; Rebecca A. Riebe; Yinghua Zhang; et al. (Journal of Molecular Medicine, 2013)

Performance of a Multi-disciplinary Emergency Department Observation Protocol for Acetaminophen Overdose - Gillian A. Beauchamp; Kimberly W. Hart; Christopher J. Lindsell; Michael S. Lyons; Edward J. Otten; Carol L. Smith; Michael J. Ward; Stewart W. Wright (Journal of Medical Toxicology, 2013)

Modeling Physical-Biological Responses to Climate Change in the California Current System - Peter Franks; Emanuele Di Lorenzo; Nicole Goebel; Fanny Chenillat; Pascal Riviere; Christopher Edwards; Arthur Miller (Oceanography, 2013)

Initial epidemic area is strongly associated with the yearly extent of soybean rust spread in North America - Christopher C. Mundt; LaRae D. Wallace; Tom W. Allen; Clayton A. Hollier; Robert C. Kemerait; Edward J. Sikora (Biological Invasions, 2013)

Functional traits explain phytoplankton responses to environmental gradients across lakes of the United States - Kyle F. Edwards; Elena Litchman; Christopher A. Klausmeier (Ecology, 2013)
Ecological communities exhibit regular shifts in structure along environmental gradients, but it has proved difficult to dissect the mechanisms by which environmental conditions determine the relative success of species. Functional traits may provide a link between environmental drivers and mechanisms of community membership, but this has not been well tested for phytoplankton, which dominate primary production in many aquatic ecosystems. Here we test whether functional traits of phytoplankton can explain how species respond to gradients of light and phosphorus across U.S. lakes. We find that traits related to light utilization and maximum growth rate can predict species' differential responses to the relative availability of these resources. These results show that laboratory‐measured traits are predictive of species' performance under natural conditions, that functional traits provide a mechanistic foundation for community ecology, and that variation in community structure is predictable in spite of the complexity of ecological communities.

Serum 25-hydroxyvitamin D and breast cancer in the military: a case–control study utilizing pre-diagnostic serum - Sharif B. Mohr; Edward D. Gorham; John E. Alcaraz; Christopher I. Kane; Caroline A. Macera; J. Kellogg Parsons; Deborah L. Wingard; Ronald Horst; Cedric F. Garland (Cancer Causes & Control, 2013)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Trait-dependent declines of species following conversion of rain forest to oil palm plantations - Michael J. M. Senior; Keith C. Hamer; Simon Bottrell; David P. Edwards; Tom M. Fayle; Jennifer M. Lucey; Peter J. Mayhew; Robert Newton; Kelvin S.-H. Peh; Frederick H. Sheldon; Christopher Stewart; Alison R. Styring; et al. (Biodiversity and Conservation, 2013)

Improving our understanding of environmental controls on the distribution of C 3 and C 4 grasses - Stephanie Pau; Erika J. Edwards; Christopher J. Still (Global Change Biology, 2013)
A number of studies have demonstrated the ecological sorting of C 3 and C 4 grasses along temperature and moisture gradients. However, previous studies of C 3 and C 4 grass biogeography have often inadvertently compared species in different and relatively unrelated lineages, which are associated with different environmental settings and distinct adaptive traits. Such confounded comparisons of C 3 and C 4 grasses may bias our understanding of ecological sorting imposed strictly by photosynthetic pathway. Here, we used MaxEnt species distribution modeling in combination with satellite data to understand the functional diversity of C 3 and C 4 grasses by comparing both large clades and closely related sister taxa. Similar to previous work, we found that C 4 grasses showed a preference for regions with higher temperatures and lower precipitation compared with grasses using the C 3 pathway. However, air temperature differences were smaller (2 °C vs. 4 °C) and precipitation and % tree cover differences were larger (1783 mm vs. 755 mm, 21.3% vs. 7.7%, respectively) when comparing C 3 and C 4 grasses within the same clade vs. comparing all C 4 and all C 3 grasses (i.e., ignoring phylogenetic structure). These results were due to important differences in the environmental preferences of C 3 BEP and PACMAD clades (the two main grass clades). Winter precipitation was found to be more important for understanding the distribution and environmental niche of C 3 PACMAD s in comparison with both C 3 BEP s and C 4 taxa, for which temperature was much more important. Results comparing closely related C 3 –C 4 sister taxa supported the patterns derived from our modeling of the larger clade groupings. Our findings, which are novel in comparing the distribution and niches of clades, demonstrate that the evolutionary history of taxa is important for understanding the functional diversity of C 3 and C 4 grasses, and should have implications for how grasslands will respond to global change.

Functional traits explain phytoplankton community structure and seasonal dynamics in a marine ecosystem - Kyle F. Edwards; Elena Litchman; Christopher A. Klausmeier (Ecology Letters, 2013)
A fundamental yet elusive goal of ecology is to predict the structure of communities from the environmental conditions they experience. Trait‐based approaches to terrestrial plant communities have shown that functional traits can help reveal the mechanisms underlying community assembly, but such approaches have not been tested on the microbes that dominate ecosystem processes in the ocean. Here, we test whether functional traits can explain community responses to seasonal environmental fluctuation, using a time series of the phytoplankton of the English Channel. We show that interspecific variation in response to major limiting resources, light and nitrate, can be well‐predicted by lab‐measured traits characterising light utilisation, nitrate utilisation and maximum growth rate. As these relationships were predicted a priori , using independently measured traits, our results show that functional traits provide a strong mechanistic foundation for understanding the structure and dynamics of ecological communities.

Greenhouse Gas Emissions from Chinese Cities - Lorraine Sugar; Christopher Kennedy; Edward Leman (Journal of Industrial Ecology, 2012)
Summary As some of the most rapidly urbanizing places in the world, China's cities have a unique relationship with global climate change. The economies found in Chinese cities are extremely resource and energy intensive; as a result, they produce significant levels of greenhouse gas (GHG) emissions. This article provides comprehensive and detailed emissions inventories for Shanghai, Beijing, and Tianjin, which were found to be responsible for 12.8, 10.7, and 11.9 tonnes of carbon dioxide equivalent per capita (t CO 2 ‐eq/capita), respectively, in 2006. The majority of emissions were from electricity production, heating and industrial fuel use, and ground transportation. The prevalence of coal in the energy supply mix (including up to 98% in Tianjin) was a fundamental cause of high energy emissions. Non‐energy emissions from industrial processes were also significant, including emissions from cement and steel production. The GHG inventories for Shanghai, Beijing, and Tianjin point to sectors requiring the most attention in terms of low‐carbon growth. Compared to ten other global cities, Chinese cities are among the highest per capita emitters, alluding to the important challenge China faces of reducing emissions while improving the quality of life for urban residents. Accordingly, this article concludes with a discussion of the opportunities and issues concerning low‐carbon growth in China, including the potential for renewable energy and the difficulties associated with emissions relocation and policy adoption.

Probing cochlear tuning and tonotopy in the tiger using otoacoustic emissions - Christopher Bergevin; Edward J. Walsh; JoAnn McGee; Christopher A. Shera (Journal of Comparative Physiology A, 2012)

Ferumoxytol-Enhanced MRI to Image Inflammation Within Human Brain Arteriovenous Malformations: a Pilot Investigation - David M. Hasan; Matthew Amans; Tarik Tihan; Christopher Hess; Yi Guo; Soonmee Cha; Hua Su; Alastair J. Martin; Michael T. Lawton; Edward A. Neuwelt; David A. Saloner; William L. Young (Translational Stroke Research, 2012)

Nasopharyngeal Necrosis After Chronic Opioid (Oxycodone/Acetaminophen) Insufflation - Christopher D. Rosenbaum; Katherine L. Boyle; Edward W. Boyer (Journal of Medical Toxicology, 2012)

Measuring the Form of Iron in Hydrothermal Plume Particles - Brandy Toner; Matthew Marcus; Katrina Edwards; Olivier Rouxel; Christopher German (Oceanography, 2012)

Allometric scaling and taxonomic variation in nutrient utilization traits and maximum growth rate of phytoplankton - Kyle F. Edwards; Mridul K. Thomas; Christopher A. Klausmeier; Elena Litchman (Limnology and Oceanography, 2012)
Nutrient utilization traits can be used to link the ecophysiology of phytoplankton to population dynamic models and the structure of communities across environmental gradients. Here we analyze a comprehensive literature compilation of four traits: maximum nutrient uptake rate; the half‐saturation constant for nutrient uptake; the minimum subsistence quota, measured for nitrate and phosphate; and maximum growth rate. We also use these traits to analyze two composite traits, uptake affinity and scaled uptake affinity. All traits tend to increase with cell volume, except for scaled uptake affinity and maximum growth rate, which tend to decline with cell volume. Most scaling relationships are the same for freshwater and marine species, although important differences exist. Most traits differ on average between major taxa, but between‐taxon variation is nearly always due to between‐taxon variation in volume. There is some evidence for between‐trait correlations that could constrain trait evolution, but these correlations are difficult to disentangle from correlation driven by cell volume. These results should enhance the parameterization of models that use size or taxonomic group to structure physiological variation in phytoplankton communities.

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Alcohol impairs brain reactivity to explicit loss feedback - Lindsay D. Nelson; Christopher J. Patrick; Paul Collins; Alan R. Lang; Edward M. Bernat (Psychopharmacology, 2011)

Fluorine-free mixed amphiphilic polymers based on PDMS and PEG side chains for fouling release applications - Harihara S. Sundaram; Youngjin Cho; Michael D. Dimitriou; Craig J. Weinman; John A. Finlay; Gemma Cone; Maureen E. Callow; James A. Callow; Edward J. Kramer; Christopher K. Ober (Biofouling, 2011)

Coordinated approaches to quantify long‐term ecosystem dynamics in response to global change - YIQI LUO; JERRY MELILLO; SHULI NIU; CLAUS BEIER; JAMES S. CLARK; AIMÉE T. CLASSEN; ERIC DAVIDSON; JEFFREY S. DUKES; R. DAVE EVANS; CHRISTOPHER B. FIELD; CLAUDIA I. CZIMCZIK; MICHAEL KELLER; et al. (Global Change Biology, 2011)
Many serious ecosystem consequences of climate change will take decades or even centuries to emerge. Long‐term ecological responses to global change are strongly regulated by slow processes, such as changes in species composition, carbon dynamics in soil and by long‐lived plants, and accumulation of nutrient capitals. Understanding and predicting these processes require experiments on decadal time scales. But decadal experiments by themselves may not be adequate because many of the slow processes have characteristic time scales much longer than experiments can be maintained. This article promotes a coordinated approach that combines long‐term, large‐scale global change experiments with process studies and modeling. Long‐term global change manipulative experiments, especially in high‐priority ecosystems such as tropical forests and high‐latitude regions, are essential to maximize information gain concerning future states of the earth system. The long‐term experiments should be conducted in tandem with complementary process studies, such as those using model ecosystems, species replacements, laboratory incubations, isotope tracers, and greenhouse facilities. Models are essential to assimilate data from long‐term experiments and process studies together with information from long‐term observations, surveys, and space‐for‐time studies along environmental and biological gradients. Future research programs with coordinated long‐term experiments, process studies, and modeling have the potential to be the most effective strategy to gain the best information on long‐term ecosystem dynamics in response to global change.

Salinity and Chlorophyll a as Performance Measures to Rehabilitate a Mangrove-Dominated Deltaic Coastal Region: the Ciénaga Grande de Santa Marta–Pajarales Lagoon Complex, Colombia - Victor H. Rivera-Monroy; Robert R. Twilley; J. Ernesto Mancera-Pineda; Christopher J. Madden; Ariel Alcantara-Eguren; E. Barry Moser; Bror F. Jonsson; Edward Castañeda-Moya; Oscar Casas-Monroy; Paola Reyes-Forero; Jorge Restrepo (Estuaries and Coasts, 2011)

Interval-counting neurons in the anuran auditory midbrain: factors underlying diversity of interval tuning - Gary J. Rose; Christopher J. Leary; Christofer J. Edwards (Journal of Comparative Physiology A, 2011)

Abundance and distribution of major groups of diazotrophic cyanobacteria and their potential contribution to N 2 fixation in the tropical Atlantic Ocean - Nicole L. Goebel; Kendra A. Turk; Katherine M. Achilles; Ryan Paerl; Ian Hewson; Amanda E. Morrison; Joseph P. Montoya; Christopher A. Edwards; Jonathan P. Zehr (Environmental Microbiology, 2010)
Summary The abundances of six N 2 ‐fixing cyanobacterial phylotypes were profiled at 22 stations across the tropical Atlantic Ocean during June 2006, and used to model the contribution of the diazotrophs to N 2 fixation. Diazotroph abundances were measured by targeting the nifH gene of Trichodesmium , unicellular groups A, B, C (UCYN‐A, UCYN‐B and UCYN‐C), and diatom‐cyanobiont symbioses Hemiaulus–Richelia , Rhizosolenia–Richelia and Chaetoceros–Calothrix . West to east gradients in temperature, salinity and nutrients [NO 3 ‐ + NO 2 ‐ , PO 4 3− , Si(OH) 4 ] showed the influence of the Amazon River plume and its effect on the distributions of the diazotrophs. Trichodesmium accounted for more than 93% of all nifH genes detected, dominated the warmer waters of the western Atlantic, and was the only diazotroph detected at the equatorial upwelling station. UCYN‐A was the next most abundant (> 5% of all nifH genes) and dominated the cooler waters of the eastern Atlantic near the Cape Verde Islands. UCYN‐C was found at a single depth (200 m) of high salinity and low temperature and nutrients, whereas UCYN‐B cells were widespread but in very low abundance (6.1 × 10 1 ± 4.6 × 10 2 gene copies l −1 ). The diatom‐cyanobionts were observed primarily in the western Atlantic within or near the high Si(OH) 4 input of the Amazon River plume. Overall, highest diazotroph abundances were observed at the surface and declined with depth, except for some subsurface peaks in Trichodesmium , UCYN‐B and UCYN‐A. Modelled contributions of Trichodesmium , UCYN‐B and UCYN‐A to total N 2 fixation suggested that Trichodesmium had the largest input, except for the potential of UCYN‐A at the Cape Verde Islands.

Slowed decomposition is biotically mediated in an ectomycorrhizal, tropical rain forest - Krista L. McGuire; Donald R. Zak; Ivan P. Edwards; Christopher B. Blackwood; Rima Upchurch (Oecologia, 2010)

The Role of the Intestinal Lymphatics in the Absorption of Two Highly Lipophilic Cholesterol Ester Transfer Protein Inhibitors (CP524,515 and CP532,623) - Natalie L. Trevaskis; Claire L. McEvoy; Michelle P. McIntosh; Glenn A. Edwards; Ravi M. Shanker; William N. Charman; Christopher J. H. Porter (Pharmaceutical Research, 2010)

Comparative genomics based on massive parallel transcriptome sequencing reveals patterns of substitution and selection across 10 bird species - AXEL KÜNSTNER; JOCHEN B. W. WOLF; NICLAS BACKSTRÖM; OSCEOLA WHITNEY; CHRISTOPHER N. BALAKRISHNAN; LAINY DAY; SCOTT V. EDWARDS; DANIEL E. JANES; BARNEY A. SCHLINGER; RICHARD K. WILSON; ERICH D. JARVIS; WESLEY C. WARREN; et al. (Molecular Ecology, 2010)
Next‐generation sequencing technology provides an attractive means to obtain large‐scale sequence data necessary for comparative genomic analysis. To analyse the patterns of mutation rate variation and selection intensity across the avian genome, we performed brain transcriptome sequencing using Roche 454 technology of 10 different non‐model avian species. Contigs from de novo assemblies were aligned to the two available avian reference genomes, chicken and zebra finch. In total, we identified 6499 different genes across all 10 species, with ∼1000 genes found in each full run per species. We found evidence for a higher mutation rate of the Z chromosome than of autosomes (male‐biased mutation) and a negative correlation between the neutral substitution rate ( d S ) and chromosome size. Analyses of the mean d N / d S ratio (ω) of genes across chromosomes supported the Hill–Robertson effect (the effect of selection at linked loci) and point at stochastic problems with ω as an independent measure of selection. Overall, this study demonstrates the usefulness of next‐generation sequencing for obtaining genomic resources for comparative genomic analysis of non‐model organisms.

A numerical study of inferred rockfish ( Sebastes spp.) larval dispersal along the central California coast - CHRISTINE H. PETERSEN; PATRICK T. DRAKE; CHRISTOPHER A. EDWARDS; STEPHEN RALSTON (Fisheries Oceanography, 2010)
Successful recruitment of marine fishes depends on survival during early life‐history stages, which is influenced by oceanic advection due to its impact on coastal trophodynamics and transport processes. Here we evaluate the influence of ocean circulation on the dispersal of rockfish ( Sebastes spp.) larvae along the central California coast using an implementation of the Regional Ocean Modeling System, driven at the surface by output from the Coupled Ocean Atmosphere Mesoscale Prediction System. Thousands of floats simulating rockfish larval propagules, constrained to follow fixed depths, were released over a broad coastal area at 2‐day intervals, and transported by simulated ocean currents at depths of 1, 7, 20, 40, and 70 m. Trajectory statistics are averaged across the 4‐yr period from January 2000 through December 2003 to reveal mean trajectory direction, net displacement, fractional cross‐shore loss, and duration of retention for different seasons. On average, near‐surface propagules originating nearshore are transported offshore during the upwelling season, whereas deeper propagules move alongshore to the north. This vertical shear vanishes during winter, with most floats moving alongshore to the north, regardless of depth. After 35 days in the water column, typical transport distances were ∼50 km for floats remaining nearshore and ∼150 km for floats over the midshelf and slope. Implications for performance of marine reserves for rockfish conservation are discussed. Our results also provide evidence for a strong semiannual pattern of coastal retention rates, with high export of near‐surface drifters during the upwelling season. In contrast, high rates of shelf retention occurred for releases at 20 m and deeper during summer, and at all depths during winter.

APPLICATIONS IN COASTAL MODELING AND FORECASTING - Pierre De Mey; Peter Craig; Fraser Davidson; Christopher Edwards; Yoichi Ishikawa; John Kindle; Roger Proctor; Keith Thompson; Jiang Zhu (Oceanography, 2009)

THE GODAE HIGH-RESOLUTION SEA SURFACE TEMPERATURE PILOT PROJECT - Craig Donlon; Kenneth Casey; Ian Robinson; Chelle Gentemann; Richard Reynolds; Ian Barton; Olivier Arino; John Stark; Nick Rayner; Pierre LeBorgne; David Poulter; Jorge Vazquez-Cuervo; et al. (Oceanography, 2009)

Intestinal Lymphatic Transport Enhances the Post-Prandial Oral Bioavailability of a Novel Cannabinoid Receptor Agonist Via Avoidance of First-Pass Metabolism - Natalie L. Trevaskis; David M. Shackleford; William N. Charman; Glenn A. Edwards; Anne Gardin; Silke Appel-Dingemanse; Olivier Kretz; Bruno Galli; Christopher J. H. Porter (Pharmaceutical Research, 2009)

Adaptive response of equine intestinal Na+/glucose co-transporter (SGLT1) to an increase in dietary soluble carbohydrate - Jane Dyer; Miran Al-Rammahi; Louise Waterfall; Kieron S. H. Salmon; Ray J. Geor; Ludovic Bouré; G. Barrie Edwards; Christopher J. Proudman; Soraya P. Shirazi-Beechey (Pflügers Archiv - European Journal of Physiology, 2009)

Near real‐time, autonomous detection of marine bacterioplankton on a coastal mooring in Monterey Bay, California, using rRNA‐targeted DNA probes - Christina M. Preston; Roman Marin; Scott D. Jensen; Jason Feldman; James M. Birch; Eugene I. Massion; Edward F. DeLong; Marcelino Suzuki; Kevin Wheeler; Christopher A. Scholin (Environmental Microbiology, 2009)
Summary A sandwich hybridization assay (SHA) was developed to detect 16S rRNAs indicative of phylogenetically distinct groups of marine bacterioplankton in a 96‐well plate format as well as low‐density arrays printed on a membrane support. The arrays were used in a field‐deployable instrument, the Environmental Sample Processor (ESP). The SHA employs a chaotropic buffer for both cell homogenization and hybridization, thus target sequences are captured directly from crude homogenates. Capture probes for seven of nine different bacterioplankton clades examined reacted specifically when challenged with target and non‐target 16S rRNAs derived from in vitro transcribed 16S rRNA genes cloned from natural samples. Detection limits were between 0.10–1.98 and 4.43– 12.54 fmole ml −1 homogenate for the 96‐well plate and array SHA respectively. Arrays printed with five of the bacterioplankton‐specific capture probes were deployed on the ESP in Monterey Bay, CA, twice in 2006 for a total of 25 days and also utilized in a laboratory time series study. Groups detected included marine alphaproteobacteria, SAR11, marine cyanobacteria, marine group I crenarchaea, and marine group II euryarchaea. To our knowledge this represents the first report of remote in situ DNA probe‐based detection of marine bacterioplankton.

The acute post-exercise response of blood pressure varies with time of day - Helen Jones; Christopher Pritchard; Keith George; Ben Edwards; Greg Atkinson (European Journal of Applied Physiology, 2008)

Aureoles of Pb(II)-enriched feldspar around monazite in paragneiss and anatectic pods of the Napier Complex, Enderby Land, East Antarctica: the roles of dissolution-reprecipitation and diffusion - Edward S. Grew; Martin G. Yates; Christopher J. L. Wilson (Contributions to Mineralogy and Petrology, 2008)

BOOK REVIEW | Fundamentals of Geophysical Fluid Dynamics - Christopher Edwards (Oceanography, 2008)

Climate, phylogeny and the ecological distribution of C4 grasses - Erika J. Edwards; Christopher J. Still (Ecology Letters, 2008)
‘C4 photosynthesis’ refers to a suite of traits that increase photosynthesis in high light and high temperature environments. Most C4 plants are grasses, which dominate tropical and subtropical grasslands and savannas but are conspicuously absent from cold growing season climates. Physiological attributes of C4 photosynthesis have been invoked to explain C4 grass biogeography; however, the pathway evolved exclusively in grass lineages of tropical origin, suggesting that the prevalence of C4 grasses in warm climates could be due to other traits inherited from their non‐C4 ancestors. Here we investigate the relative influences of phylogeny and photosynthetic pathway in determining the ecological distributions of C4 grasses in Hawaii. We find that the restriction of C4 grasses to warmer areas is due largely to their evolutionary history as members of a warm‐climate grass clade, but that the pathway does appear to confer a competitive advantage to grasses in more arid environments.

Macroinvertebrate drift density in relation to abiotic factors in the Missouri River - Christopher H. Hay; Thomas G. Franti; David B. Marx; Edward J. Peters; Larry W. Hesse (Hydrobiologia, 2008)

Modelling the vertical distribution of Prochlorococcus and Synechococcus in the North Pacific Subtropical Ocean - Sophie Rabouille; Christopher A. Edwards; Jonathan P. Zehr (Environmental Microbiology, 2007)
Summary A simple model was developed to examine the vertical distribution of Prochlorococcus and Synechococcus ecotypes in the water column, based on their adaptation to light intensity. Model simulations were compared with a 14‐year time series of Prochlorococcus and Synechococcus cell abundances at Station ALOHA in the North Pacific Subtropical Gyre. Data were analysed to examine spatial and temporal patterns in abundances and their ranges of variability in the euphotic zone, the surface mixed layer and the layer in the euphotic zone but below the base of the mixed layer. Model simulations show that the apparent occupation of the whole euphotic zone by a genus can be the result of a co‐occurrence of different ecotypes that segregate vertically. The segregation of ecotypes can result simply from differences in light response. A sensitivity analysis of the model, performed on the parameter α (initial slope of the light‐response curve) and the DIN concentration in the upper water column, demonstrates that the model successfully reproduces the observed range of vertical distributions. Results support the idea that intermittent mixing events may have important ecological and geochemical impacts on the phytoplankton community at Station ALOHA.

Increasing the Proportional Content of Surfactant (Cremophor EL) Relative to Lipid in Self-emulsifying Lipid-based Formulations of Danazol Reduces Oral Bioavailability in Beagle Dogs - Jean F. Cuiné; William N. Charman; Colin W. Pouton; Glenn A. Edwards; Christopher J. H. Porter (Pharmaceutical Research, 2007)

Evolutionary genetics of Carpodacus mexicanus, a recently colonized host of a bacterial pathogen, Mycoplasma gallisepticum - Christopher M. Hess; Zhenshan Wang; Scott V. Edwards (Genetica, 2007)

Degradation of water quality in Lough Neagh, Northern Ireland, by diffuse nitrogen flux from a phosphorus‐rich catchment - Lynda Bunting; Peter R. Leavitt; Christopher E. Gibson; Edward J. McGee; Valerie A. Hall (Limnology and Oceanography, 2007)
Annually resolved fossil records of nitrogen (N) inputs (as sedimentary δ 15 N, N content), aquatic production (δ 13 C, C content), and algal abundance and gross community composition (pigments, nonsiliceous microfossils) from Lough Neagh, Northern Ireland (NI), were compared with annual records of climatic variability, atmospheric and urban nutrient loading, whole‐catchment nutrient budgets, and limnological monitoring data to identify the unique effects of N on the eutrophication of a phosphorus (P)‐rich lake during ca. 1933‐1995. Cluster analysis revealed two major biostratigraphic zones. Zone I (ca. 1933–1955) was characterized by moderate lake production, as inferred from low concentrations of most fossil pigments and reduced δ 15 N signatures but elevated δ 13 C values and chlorophyte microfossil concentrations. In contrast, Zone II (ca. 1955‐1995) exhibited greatly increased contents of 15 N, N, C, and algal pigments, combined with strongly reduced δ 13 C ratios and chlorophyte fossil abundance, a pattern consistent with recent severe eutrophication. Overall, microfossils of diazotrophic cyanobacteria were most abundant during the transition period between zones (ca. 1955‐1964). Regression analysis revealed that past N influx to the lake (as δ 15 N; r 2 = 0.916, p 2 = 0.837, p 2 = 0.388, p 2 δ 15 N = 0.503, p 2 cyanobacteria = 0.296, p 2 total algae = 0.046, p

The Absorption of Darbepoetin Alfa Occurs Predominantly via the Lymphatics Following Subcutaneous Administration to Sheep - Danielle N. McLennan; Christopher J. H. Porter; Glenn A. Edwards; Anne C. Heatherington; Steven W. Martin; Susan A. Charman (Pharmaceutical Research, 2006)

Primary production in Long Island sound - Nicole L. Goebel; James N. Kremer; Christopher A. Edwards (Estuaries and Coasts, 2006)

An indirect test of inbreeding depression in the termites Reticulitermes flavipes and Reticulitermes virginicus - Christopher J. DeHeer; Edward L. Vargo (Behavioral Ecology and Sociobiology, 2006)

Two-locus genome-wide linkage scan for prostate cancer susceptibility genes with an interaction effect - Bao-Li Chang; Ethan M. Lange; Latchezar Dimitrov; Christopher J. Valis; Elizabeth M. Gillanders; Leslie A. Lange; Kathleen E. Wiley; Sarah D. Isaacs; Fredrik Wiklund; Agnes Baffoe-Bonnie; Carl D Langefeld; S. Lilly Zheng; et al. (Human Genetics, 2006)

Phosphodiesterase inhibition by sildenafil citrate attenuates a maze learning impairment in rats induced by nitric oxide synthase inhibition - Bryan D. Devan; Jonna L. Bowker; Kara B. Duffy; Ila S. Bharati; Mariana Jimenez; Demetrio Sierra-Mercado; Christopher M. Nelson; Edward L. Spangler; Donald K. Ingram (Psychopharmacology, 2006)

Hydroxyl and Peroxy Radical Chemistry in a Rural Area of Central Pennsylvania: Observations and Model Comparisons - Xinrong Ren; William H. Brune; Christopher A. Cantrell; Gavin D. Edwards; Terry Shirley; Andrew R. Metcalf; Robert L. Lesher (Journal of Atmospheric Chemistry, 2005)

Susceptibility to Lipase-Mediated Digestion Reduces the Oral Bioavailability of Danazol After Administration as a Medium-Chain Lipid-Based Microemulsion Formulation - Christopher J. H. Porter; Ann Marie Kaukonen; Ben J. Boyd; Glenn A. Edwards; William N. Charman (Pharmaceutical Research, 2004)

Colony genetic organization and colony fusion in the termite Reticulitermes flavipes as revealed by foraging patterns over time and space - Christopher J. Deheer; Edward L. Vargo (Molecular Ecology, 2004)
Temporal and spatial analyses are seldom utilized in the study of colony genetic structure, but they are potentially powerful methods which can yield novel insights into the mechanisms underlying variation in breeding systems. Here we present the results of a study which incorporated both of these dimensions in an examination of genetic structure of subterranean termites in the genus Reticulitermes ( primarily R. flavipes ). Most colonies of this species (70%) were simple families apparently headed by outbred primary reproductives, while most of the remaining (27% of the total) colonies contained low effective numbers of moderately inbred reproductives. Mapping the spatial distribution of colony foraging sites over time revealed that despite the high colony density, the absolute foraging boundaries of most R. flavipes colonies were persistent and exclusive of other conspecific colonies, which suggests that this species is more territorial than has been implied by laboratory studies of intraspecific aggression. Nevertheless, we found a single colony (3% of all colonies) which contained the offspring of more than two unrelated reproductives. Although other studies have also described subterranean termite colonies with a similarly complex genetic composition, we demonstrate here that such colonies can form under natural conditions via the fusion of whole colonies. This study underscores how repeated sampling from individual colonies over time and space can yield information about colony spatial and genetic structure that cannot be obtained from conventional analyses or sampling methods.

Intestinal Lymphatic Transport of Halofantrine Occurs After Oral Administration of a Unit-Dose Lipid-Based Formulation to Fasted Dogs - Shui-Mei Khoo; David M. Shackleford; Christopher J. H. Porter; Glenn A. Edwards; William N. Charman (Pharmaceutical Research, 2003)

Pharmacokinetic Model to Describe the Lymphatic Absorption of r-metHu-Leptin After Subcutaneous Injection to Sheep - Danielle N. McLennan; Christopher J. H. Porter; Glenn A. Edwards; Maria Brumm; Steven W. Martin; Susan A. Charman (Pharmaceutical Research, 2003)

Class I molecules with similar peptide-binding specificities are the result of both common ancestry and convergent evolution - Alessandro Sette; John Sidney; Brian D. Livingston; John L. Dzuris; Claire Crimi; Christopher M. Walker; Scott Southwood; Edward J. Collins; Austin L. Hughes (Immunogenetics, 2003)

Creatine supplementation during college football training does not increase the incidence of cramping or injury - Michael Greenwood; Richard B. Kreider; Charlie Melton; Christopher Rasmussen; Stacy Lancaster; Edward Cantler; Purvis Milnor; Anthony Almada (Molecular and Cellular Biochemistry, 2003)

Long-term creatine supplementation does not significantly affect clinical markers of health in athletes - Richard B. Kreider; Charles Melton; Christopher J. Rasmussen; Michael Greenwood; Stacy Lancaster; Edward C. Cantler; Pervis Milnor; Anthony L. Almada (Molecular and Cellular Biochemistry, 2003)

Reproduction of hatchery-reared and transplanted wild bay scallops, Argopecten irradians irradians, relative to natural populations - Stephen T. Tettelbach; Christopher F. Smith; Peter Wenczel; Edward Decort (Aquaculture International, 2002)

1H NMR investigations of the molecular nature of low-molecular-mass calcium ions in biofluids - Christopher J. Silwood; Martin Grootveld; Edward Lynch (JBIC Journal of Biological Inorganic Chemistry, 2002)

Lymphatic Absorption Is a Significant Contributor to the Subcutaneous Bioavailability of Insulin in a Sheep Model - Susan A. Charman; Danielle N. McLennan; Glenn A. Edwards; Christopher J. H. Porter (Pharmaceutical Research, 2001)

The CD45 locus in cattle: allelic polymorphism and evidence for exceptional positive natural selection - Keith T. Ballingall; Lillian Waibochi; Declan J. McKeever; Edward C. Holmes; Christopher H. Woelk; Niall D. MacHugh; Vittoria Lutje (Immunogenetics, 2001)

Isolation and identification of a 92-kDa stress induced protein from Candida albicans - Edward T. Burt; Christopher O'Connor; Bryan Larsen (Mycopathologia, 1999)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Lead transport in IEC-6 intestinal epithelial cells - Christopher M. Dekaney; Edward D. Harris; Gerald R. Bratton; Laurie A. Jaeger (Biological Trace Element Research, 1997)